Cross-provincial electricity allocation and regional energy development: Evidence from China's ultra-high voltage grid expansion - Bao-Jun Tang; Pei-Yun Xu; Ru Li; Chong-Zhou Wang (Utilities Policy, 2026)

Structure and characteristics of quercetin-loaded starch nanoparticles and their surface charges for protein corona formation with gastrointestinal digestive enzymes - Yu-Ru Wu; Zhi-Yuan Yang; Shan-Dan Zhao; Dan-Yang Shen; Ya-Jun Lin; Yi-Bin Zhou; Kang Liu (Food Hydrocolloids, 2026)

Nanoconfinement of Prussian blue ionic liquid-MOF nanocrystal material for cesium adsorption - Shuang-Long Wang; Yue-Ru Zhou; Guo-Hong Tao; Ling He (Chemical Engineering Journal, 2026)

Vascular bundle adaptation to water-salt stress in sweet sorghum: An integrated anatomical and physiological pathway analysis - Xinjie Shi; Ru Zhou; Chunyu Wang; Ling Li; Donghao Li (Plant Science, 2026)

Uranium in-situ leaching: Combining conditional deep convolutional generative adversarial network (cDC-GAN) and ensemble smoother with multiple data assimilation (ES-MDA) to estimate the heterogeneous permeability coefficient field - Wen-gui Ji; Yue Luo; Bing Wang; Yi-ru Zhou; Yan-hong Zhang; Xian-ping Luo (Hydrometallurgy, 2026)

Electroacupuncture-induced gut microbiota alterations correlate with FXR/FGF15 activation and metabolic improvement in hyperlipidemic rats - Huan Wu; Li Zhou; Wei Lin; Hong-xing Zhang; Zhao-qing Zhang; Xiao-fei Wang; Shi-ru Ju; Zhi-gang Liu; Fei Hu (Advances in Traditional Medicine, 2026)

Complete mitochondrial genomes and phylogenetic analysis of three species of Indo-Pacific freshwater gobies, Stiphodon (Gobiiformes, Oxudercidae) - Cheng-He Sun; Xian-Ru Li; Su-Fan Zhou; Yan-Zi Zhong; Xiao Ma; Xiao-Die Chen (Journal of Genetics, 2026)

Integration of niche evolution and pre-adaptation shaped the diversity of Cypripedium (Orchidaceae) in subtropical and temperate regions since mid-Miocene times - Liu-Qiong Wei; Peng Zhou; Pei-Yang Zhang; Si-Xian Li; Bo-Ni Lai; Ru-Yang Ye; Ji-Hong Li; Yan Luo; Xiao-Hong Zeng; Yi-Zhen Liu; Xiao-Guo Xiang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Asymmetric evolution of capturability of atmospheric water (CAW) across global arid and humid regions - Hou-Liang Lu; Hong-Ru Wang; Hui-Min Zuo; Han Zhou; Yu-Fei Jiao; Bill X. Hu (Journal of Hydrology, 2026)

Regulation mechanisms of torrefaction atmospheres on structural evolution, pyrolysis behavior, and product distribution of corn straw - Jusheng Hu; Zihang Zhang; Hongcai Su; Shaojie Zhou; Gongxin Dai; Bin Ru; Shurong Wang (Fuel, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

A comparative observational study of prokaryotic microbial community dynamics across different Litopenaeus vannamei cultivation systems - Chaosheng Zhou; Yue Wu; Maocang Yan; Rongmao Lu; Xiaolin Huang; Shaoguo Ru (Frontiers in Marine Science, 2026)
Introduction Microbial communities are key indicators of ecosystem health in aquaculture, yet their temporal dynamics under different cultivation systems remain poorly characterized. This study compares prokaryotic community succession across three commercial Litopenaeus vannamei cultivation systems with contrasting pond construction, salinity, and water-exchange intensity. Methods We collected 85 water samples from five sub-ponds per system at 15-day intervals and characterized prokaryotic communities via 16S rRNA amplicon sequencing, combined with α/β diversity, LEfSe, and PICRUSt2-based functional analyses. Results Community composition and diversity differed markedly among systems: α-diversity was highest in the earthen brackish pond (EBXS) and lowest in the concrete seawater pond (HSDT). Proteobacteria dominated all systems, while Actinobacteria prevailed in EBXS, which also showed increasing relative abundances of potentially pathogenic genera (Aeromonas, Mycobacterium, Rickettsia) over time. HSDT exhibited the highest predicted metabolic potential (90 enriched KEGG pathways). Temporally, EBXS displayed more stable succession and higher overall similarity, whereas high-level ponds showed greater species turnover. Discussion Salinity and cultivation system emerged as major correlates of community variation, though inherently confounded in our observational design. These patterns suggest a trade-off between community stability and pathogenic risk across production strategies. Our findings offer empirical baselines and testable hypotheses for future controlled studies to disentangle the individual effects of salinity, pond construction, and water management on microbial assembly in aquaculture systems.

Comparative study on combustion characteristics of dual-fire sources in naturally ventilated tunnels: Effects of fuel type and spacing - Wenhao Xue; Yuan Wang; Yang Lou; Xinlei Liu; Ru Zhou; Min Hao; Juncheng Jiang (Tunnelling and Underground Space Technology, 2026)

Paedocin A: An undescribed iridoid with a C1-C4 ether linkage from Paederia foetida with hepatoprotective effects - Wan-Qi Zhang; Xin-Yue Li; Ming-Hui Sun; Jie Zhou; Guo-Ru Shi; De-Quan Yu; Yan-Fei Liu (Phytochemistry Letters, 2026)

Waste cotton textiles-derived cellulose superhydrophobic aerogel for efficient oil-water separation - Ya-hui Li; Hui-Jiang; Xiao-quan Zhu; Ru-ru Ma; Er-min Zhou; Jun-li Luo; De-qiang Li; Hong-tao Jia; Jun Li; Lu-xiang Wang (Journal of Water Process Engineering, 2026)

Particulate matter-bound metals and chlorinated paraffins co-exposure: A population-based study on attention-deficit/hyperactivity disorder in Chinese youth - Ya-Qin Zhang; Qi Yang; Hai-Xin Tu; Haseeb Tufail Moryani; Wan-Ting He; Jing-Wen Huang; Dan-Yao Zhou; Yun-Ting Zhang; Li-Xia Liang; Yang Zhou; Li-Zi Lin; Wen-Wen Bao; et al. (Journal of Hazardous Materials, 2026)

Achieving ultrahigh water evaporation using g-C3N4/MoS2/chitosan hydrogel@nickel foam evaporator with low enthalpy and optimized scallion-like structure - Zeen Xu; Xingyue Lei; Ru Jiang; Leihao Zhou; Shentao Jiang; Xianqiang Xiong; Qi Wang; Jianbing Li; Huayue Zhu (Chemical Engineering Journal, 2026)

FOXG1 Transcriptionally Orchestrates Parvalbumin+ Interneuron Function Contributing to Schizophrenia Pathology - Pengfei Jiang; Mingzhao Su; Xue Zhou; Baoshen Zhang; Jie Sun; Ru Ba; Junhua Liu; Chunjie Zhao (Neuroscience Bulletin, 2026)
Schizophrenia (SCZ) is characterized by heterogeneous symptoms including abnormal perception, social withdrawal, and cognitive deficits. Parvalbumin-positive (PV + ) interneurons are particularly vulnerable in SCZ; however, the underlying cellular basis remains unclear. In this study, we found that selective deletion of the SCZ risk gene Foxg1 in PV + interneurons of mice recapitulated aspects of the disease phenotype, including impaired sensorimotor gating, anxiety-like behavior, social deficits, and cognitive impairments. Foxg1 deficiency caused dendritic simplification, reduced spine density, and impaired synaptic transmission in PV + interneurons of the prelimbic cortex. Our findings indicate that FOXG1 directly drives a set of SCZ risk genes that encode synaptic receptors, adhesion molecules, scaffolding proteins, transporters, ion channels, and vesicle-trafficking proteins, thereby orchestrating PV + interneuron synaptic function. Notably, FOXG1 activates the transcription of metabotropic glutamate receptor 3 (mGluR3), and pharmacological potentiation of mGluR3 activity alleviates behavioral deficits in Foxg1 conditional knockout mice. In conclusion, our findings identify a novel role for Foxg1 in PV + interneurons, providing new mechanistic insights into their vulnerability to SCZ.

Curcumol induces autophagy-dependent hepatic stellate cell death through methionine metabolism disruption - Yi-jie Gao; Ya Zhou; Yi-ning Li; Kai-yao Yang; Si-wei Xia; Meng-ru Hu; Yang Li; Li Chen; Fei-xia Wang; Shuai Lu; Na-qi Lian; Shi-zhong Zheng; et al. (Toxicology and Applied Pharmacology, 2026)

Bioactive PVA/SDES propolis extracts composite films for extending oyster shelf life: Structure, functionality, and preservation performance - Tian Du; Lin-Kun Sun; Pei-Ru Zhou; Yu-Cang Zhang; Yan-Zhen Zheng (Food Packaging and Shelf Life, 2026)

Structural Prior-Guided Adaptive Wavelet Denoising for Single-Channel Dolphin Whistles - Ru Wu; Xiang Zhou; Wen Chen; Peibin Zhu; Xiaomei Xu (Journal of Marine Science and Engineering, 2026)
The continuous, narrowband time-frequency structure of dolphin whistles is an important information carrier for target detection, behavioral analysis, and ecological monitoring in passive acoustic monitoring. However, ocean noise can easily obscure whistle time-frequency contours, blur their boundaries, and cause local discontinuities, thereby reducing the reliability of subsequent acoustic analysis. Existing denoising methods based on transform-domain thresholding and spectral-domain statistical modeling can attenuate background interference to some extent. However, without explicit structural constraints, these methods still have difficulty achieving a satisfactory balance between noise suppression and preservation of the whistle time–frequency structure. To address this problem, this study proposes a Structural Prior-Guided Adaptive Wavelet Denoising (SPG-AWD) method for single-channel unsupervised scenarios. The proposed method introduces structural priors at two levels: adaptive subband selection and terminal node denoising. At the first level, subband nodes are adaptively split, retained, or suppressed based on stationary wavelet packet recursive decomposition and the distribution of candidate structures. At the second level, a structural mask satisfying local grouped-energy and two-dimensional time–frequency connectivity constraints is extracted, and a continuous whistle-presence probability is obtained through a signed distance transform. This probability is then used to jointly guide local noise power spectral density estimation and protective Wiener gain fusion. Simulation results show that, under real recorded background noise and ship noise conditions, SPG-AWD achieves favorable overall denoising performance when the input SNR is higher than −16 dB, while maintaining a more stable balance between target region energy preservation and non-target region noise suppression. Experiments on real recordings further demonstrate that the proposed method can effectively suppress in-band noise components within the whistle-bearing frequency range, better preserve continuous main frequency contours, and improve the overall perceptibility of whistle contours, confirming its applicability to single-channel dolphin whistle denoising in complex underwater noise environments.

A regional classification framework integrating AI and causal inference revealing the drivers of lake eutrophication in China - Yong Xu; Ru-Long Ma; Yu-Xi Feng; Bin Zou; Shen-Xin Li; Wen-Ting Huang; Shang-Chen Zhou; Wen-Qiang Peng (Water Research, 2026)

Superoxide dismutase/peroxidase-like MoS2 quantum dots enhance ammonia synthesis by Klebsiella pasteurii - Meng-Xin Zhao; Si-Ru Chen; Shan-Shan Hu; Ting-Ting Liu; Jia-Le Teng; Ya-Wen Yu; Jia-Long Zhang; Xue-Ru Zhou; Qun-Feng Ye; Su-Fang Qin; Le-Xing You (Journal of Environmental Chemical Engineering, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Terbium chloride post-treatment for highly efficient and stable Sb2(S,Se)3 solar cells - Shengquan Shan; Jihao Ma; Yang Chen; Lun Zhang; Chengyang Wang; Yanrui Yang; Ru Zhou; Mei Lyu; Jun Zhu (Chemical Engineering Journal, 2026)

Quantifying summer land surface cooling performance of parks and population accessibility across urban–rural gradients in subtropical megaregions - Qianyi Bei; Wenzhuo Luo; Xinyin Li; Jiangdi Ru; Siyu Zhou; Jing Xie (Building and Environment, 2026)

Characteristic of ocean surface wave across the mesoscale eddies during tropical cyclones in the South China Sea - Ru Yao; Weizeng Shao; Xingwei Jiang; Qingping Zou; Lei Zhou (Ocean Dynamics, 2026)

Brain Serotonin Deficiency Impairs Ovarian Reserve Function via the Hypothalamic-Pituitary-Ovarian Axis - Shuang-Shuang Cui; Zhuo-Nan Yang; Jin Xiao; Jin-Ping Qiao; Yue-Ming Zhang; Ling-Ge Shi; Hui-Ru Cheng; Si-Min Ding; Meng-Yao Wang; Dong-Mei Ji; Tao Zhang; Dan Liang; et al. (Neuroscience Bulletin, 2026)

Exploring the characteristics of smoke back-layering during lithium-ion battery fires in confined tunnel spaces - Yuan Wang; Wenhao Xue; Zhaojie Zhu; Yang Lou; Ru Zhou; Min Hao; Juncheng Jiang (Process Safety and Environmental Protection, 2026)

Green manure co-application boosts arid agroecosystem sustainability: Mixed sowing of feed rape and hairy vetch modulates N input and enzymes for optimized wheat production - Ru Yu; Jie Zhou; Fangdi Chang; Jiashen Song; Jing Wang; Xiaobin Li; Hua Zhang; Jufeng Cao; Xiaohong Li; Hanjiang Liu; Hongyuan Zhang; Yuyi Li (Field Crops Research, 2026)

A 2000-year record of polycyclic aromatic hydrocarbon deposition in Lake Basongcuo, southeast Tibet: Source apportionment and implications for human impacts - Ru Guo; Jinglu Wu; Jianchao Zhou; Miao Jin (Journal of Environmental Management, 2026)

Anodic potential and conductive carrier synergistically drive nitrite-free extracellular electron transfer-dependent anaerobic ammonium oxidation (Anammox) in mixed microbial communities - Yang-Guang Xia; Jun-Hong Zhou; Xiao-Li Yang; Fei-Fan Shi; Ru Fan; Jia-Ying Xu (Bioresource Technology, 2026)

Molecular identification and genetic diversity of Echinococcus granulosus sensu stricto in livestock from Qinghai lake on the Qinghai-Tibetan plateau - Jun He; Guoyan Zhou; Fan Zhang; Hongrun Ge; Ao Chen; Ru Meng; Zhihong Guo; Yijuan Ma; Yong Fu (Veterinary Research Communications, 2026)

Novel biodiversity and biogeography insights of filamentous Bangiales (Rhodophyta) from China - Yan-De Wang; Yin-Yin Deng; Cui-Cui Tian; Han-Ru Ge; Wei Zhou; Nan-Jing Ji; Li-En Yang (Algae, 2026)
The taxonomy of filamentous Bangiales was challenging due to its plastic and simple morphology. Molecular approaches play a significant role in revealing cryptic biodiversity and resolving phylogenetic relationships. Nonetheless, the biodiversity of filamentous Bangiales in many regions, including China, has not been thoroughly investigated yet using updated methods. In this study, we investigated the biodiversity of filamentous Bangiales in China, employing a more comprehensive and detailed sampling approach. The rbcL and 18S gene sequences (partial or complete) of 49 specimens collected from 37 sites were obtained. Phylogenetic analysis resolved these specimens into four clades, including Bangia, ‘Bangia’ 1, ‘Bangia’ 2, and Pseudoganglia. Seven putative species were delineated using empirical methods, including Automatic Barcode Gap Discovery (ABGD), General Mixed Yule Coalescent (GMYC), and Bayesian Poisson tree processes (bPTP), as well as genealogical analysis. Among them, four were species previously reported, two were cryptic species, and the other was a new record in China. The distribution of these molecularly delineated species was mapped along China’s coastline. Similar to the bladed Bangiales, antitropical, transoceanic, and thermal-gradient distribution patterns were also observed for filamentous Bangiales on a global scale. The ancestral region was retraced by incorporating species data from China into existing datasets using BioGeoBEARS with BAYAREALIKE + J as the best-supported model. Under this model, East Asia shows the highest marginal probability as the ancestral area for the crown clade, though uncertainty remains across alternative regions. A most parsimonious expansion scenario of Bangiales from east Gondwana to other regions of the world was proposed.

Triterpenoids from Ganoderma angustisporum and their α -glucosidase inhibitory activities - Fan-Ru Xu; Le Zhou; Yu-Cheng Dai; Hai-Sheng Yuan; Yu-Xi Wang (Natural Product Research, 2026)

Cyclopentanoid monoterpene glycosides from the aerial parts of Paederia foetida L - Wan-Qi Zhang; Xin-Yue Li; Ming-Hui Sun; Jie Zhou; Guo-Ru Shi; De-Quan Yu; Yan-Fei Liu (Phytochemistry, 2026)

Microplastic-pathogen interactions differentially modulate tomato Fusarium wilt severity: The dependence of polymer biodegradability - Siqi Shen; Yawei Zhou; Ru Zhao; Meng Liu; Wenjiang Fu; Shuting Zhao; Chaokai Yan; Qi Gao; Dan Zhang; Yanhua Wang; Hanzhong Jia; Yahong Wei (Journal of Hazardous Materials, 2026)

Biovoltage-driven, sulfurized Fe–Co anode promoted the generation of salt source active species for enhanced antibiotic removal - Shengtao Jiang; Jie Fang; Hao Zhou; Xiaojun Wang; Haoyang Liu; Deman Han; Ru Jiang; Yutong Cai; Yiting Shi; Yanbiao Liu (Journal of Environmental Management, 2026)

Mechanism of adsorption and biodegradation of typical antibiotics by sediments in mariculture tailwater system - Jun-Ru Zhao; Xing Li; Yan-Ling Yang; Zhi-Wei Zhou; Ze-Dong Lu; Xiao-Yan Fan (Environmental Research, 2026)

Relationship of serum polycyclic aromatic hydrocarbon (PAHs) and lung function in adults: Evidence from a large community-based population in Guangzhou, China - Jing-Lin Zhang; Nuo Chen; Shui-Yue Lu; Michael S. Bloom; Shao Lin; Lu-Yin Wu; Li-Xia Liang; Yun-Ting Zhang; Jing-Wen Huang; Muhammad Amjad; Yong-Xiang Tang; Zhao-Huan Gui; et al. (Environmental Research, 2026)

Tracking the dynamic changes in vegetation belts in China: spatiotemporal insights into climate and human influences - Yong Xu; Yun-Gui Lu; Qiang-Yu Dai; Wen-Ting Huang; Shang-Chen Zhou; Ru-Long Ma; Wen-Qiang Peng; Yu-Xi Feng (Regional Environmental Change, 2026)

Construction of acyl-homoserine lactone-producing engineered bacteria for activating low-temperature anammox process - Jiangwei Wang; Jianhang Zhou; Yiming Feng; Jingqi Sun; Ru Zheng; Kuo Zhang; Juejun Pan; Xiaogang Wu; Liguo Zhang; Sitong Liu (Environmental Research, 2026)

Tree of life and conservation of gymnosperms in China - Chang-Wang Ma; Dan Xie; Hong Du; Kai-Yuan Huang; Yuan-Yuan Feng; Zhou-Rui Wei; Xin-Quan Liu; Cheng-Ru Li; Jing-Jing Sun; Xiao-Xin Wei; Zhi-Heng Wang; Wei-Hua Xu; et al. (Science China Life Sciences, 2026)

The protective effects of alkaloids from Stephania tetrandra S. Moore on H9C2 cardiomyocytes - Yan-nan Ji; Ran Zhou; Zhi-hui Zhang; Xing-ru Gao; Si-qian Yang; Pu-yu Yang; Zi-shan Chen; Jun-li Sha; Jing-yu He; Yue-feng Zhang; Tie-jun Zhang; Yu-cheng Gu; et al. (Natural Product Research, 2026)

Near-full-component sewage sludge valorization via integrated alkali-mediated pyrolysis and sub-boiling temperature crystallization of hierarchical carbon-zeolite composites from carbonaceous and inorganic constituents - Zhihang Yuan; Houmin Yin; Jicui Cui; Changfu Yang; Zhou Zhen; Xiaohan Cui; Yumeng Jin; Lifeng Lin; Long Kong; Ruina Zhang; Ruyi Wang; Lei Che; et al. (Water Research, 2026)

Long-term ozone exposure and attention-deficit/hyperactivity disorder symptoms in school-aged children: Findings from a large multi-city study in China - Zhao-Huan Gui; Wan-Ting He; Yun-Ting Zhang; Joachim Heinrich; Michael S. Bloom; Shao Lin; Bin Jalaludin; Mohammed Zeeshan; Lidia Morawska; Tian-Yu Zhao; Shyamali Dharmage; Luke Knibbs; et al. (Journal of Hazardous Materials, 2026)

Straw interlayer burial improved soil humic fractions via pore-microbe mediated life strategy hierarchy regulating pore structure and bacterial characteristic in saline soils - Hongyuan Zhang; Jiashen Song; Jie Zhou; Fangdi Chang; Ru Yu; Wenhao Feng; Haoruo Li; Jing Wang; Xiaobin Li; Yuyi Li (Journal of Environmental Management, 2026)

Zinc isotopes equilibrium fractionation induced by α-Al2O3 surface adsorption and its implications: A density functional theory study - Yin-Chuan Li; Hai-Zhen Wei; Martin R. Palmer; Ya-Ru Zhou; Hao-Long Li; Zhi-Jie Liu; Yong-Hui Li (Geochimica et Cosmochimica Acta, 2026)

Untargeted metabolomics elucidates the enhanced protective effects of blackberry juice fermented with Lacticaseibacillus paracasei on hypothalamic-pituitary-adrenal (HPA) axis neuronal dysfunction - Han Wu; Qing-Ru Di; Anthony Pius Bassey; Shu-Dong Xie; Maria G. Corradini; Jian-Zhong Zhou; Xiao-Li Liu (Food Chemistry, 2026)

Sustainable extraction and bioconversion of tea stems using NADES: Dual benefits in polyphenolic recovery and carbohydrates enzymatic hydrolysis - Lin-Kun Sun; Pei-Ru Zhou; Tian Du; Yu-Cang Zhang; Yan-Zhen Zheng (Food Chemistry, 2026)

Associations of particulate matter size fractions and chemical composition with conjunctivitis and eczema: epidemiological evidence from the Pearl River Delta, China - Lu-Yin Wu; Mohammed Zeeshan; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Wen-Wen Bao; Yang Zhou; Muhammad Amjad; Li-Zi Lin; Ru-Qing Liu; Zhi Wang; Guang-Hui Dong (Environmental Research, 2026)

Reconstructing historical cloud ice water fraction using machine learning and multi-source satellite data from 1983 to 2009 - Dezhi Xiao; Chunsong Lu; Sinan Gao; Jiashan Zhu; Yang Li; Ru Zhou; Junjun Li; Jing Yang; Naifu Shao (Atmospheric Research, 2026)

Continuous Removal of Fluoride by Fe/Al-Anchored Bamboo Charcoal in Fixed Bed Column and Prediction of Breakthrough Curve using Artificial Neural Network Model - Shuqin Bai; Ru Ya; Wei Ding; Xiaohua Xie; Mingjun Zhou; Guojing Zhao; Tianxu Yang (Water, Air, & Soil Pollution, 2026)

Inhibition of the Microglial cGAS-STING Pathway Improves Neurological Deficits and Long-Term Hydrocephalus Symptoms in Mice with Intraventricular Hemorrhage - Hao-Xiang Wang; Hua-Jiang Deng; Kun-Hong Zhong; Zi-Ang Deng; Bao-Cheng Gao; Xin Tang; Yuan-You Li; Ke-Ru Huang; Ai-Ping Tong; Da-Xiong Feng; Liang-Xue Zhou (Molecular Neurobiology, 2026)

Overlooked Roles of Pharmaceutical Metabolic Products in Stimulating Microbial Metabolism and Antibiotic Resistance Gene Dissemination of Anaerobic Sludge - Jing Wu; Dan Sun; Yuan Pan; Dong‐Feng Liu; Hui Zhang; Jun‐Hua Zhou; Tong Gao; Jie Wu; Ru‐Li He; Yin‐Guang Chen; Wen‐Wei Li (Environmental Microbiology, 2026)
The roles of non‐antibiotic pharmaceuticals in shaping the dissemination behaviours of antibiotic resistance genes (ARGs) in wastewater treatment systems remain poorly understood, and the influences of their transformation products have been overlooked. Here, we unveil more profound impacts of the metformin (MET) biotransformation product than the parent pollutant on the microbial community structure and ARG propagation of wastewater anaerobic sludge. The exposure to MET and its metabolic products guanylurea (GUA) at environmentally relevant concentrations both raised the methane production and resulted in up to 52.5% higher sludge ARGs abundance relative to the unexposed control. Especially, the GUA group showed up to 188‐fold upregulation in several ARGs including bcrA , PmrF , acrB and mexF , enabled 3218‐fold enrichment of plasmids from several bacteria. The underlying mechanisms were elucidated by integrated metagenomics, molecular dynamics simulations, and metabolic profiling analyses. MET and GUA were found to trigger coordinated cellular responses including disrupted glycerophospholipid metabolism, increased membrane permeability and broad metabolic reprogramming, which collectively boosted the ARGs dissemination. Overall, this work establishes a mechanistic link between micropollutant‐induced microbial stress and ARGs propagation in anaerobic sludge, and advocates for re‐evaluating the environmental risks of non‐antibiotic pharmaceuticals and integrating resistance control into wastewater management framework.

Influence of ambient wind on temperature distribution and smoke propagation in urban road tunnels with vertical shafts during fires - Peng Wu; Zhonghao Wen; Hongzhe Zhong; Ru Zhou; Min Hao; Juncheng Jiang (Tunnelling and Underground Space Technology, 2025)

Numerical simulations and theoretical analysis of ambient wind impact on shaft smoke exhaust performance in tunnel fires - Peng Wu; Junwei Chi; Ru Zhou; Min Hao; Juncheng Jiang (Tunnelling and Underground Space Technology, 2025)

7,8-Dihydroxyflavone attenuates cisplatin-induced cardiomyocyte apoptosis and mitochondrial dysfunction via the p53/Nrf2 pathway - Zhen Tian; Ting-ting Tan; Yu-wei Hu; Jia-tong Yao; Xiao-ting Kang; Jin-yu Zhou; Dong-xu Jia; Qing-liu Li; Ru-jin Liang; Li-mei Zhao; Hua Zhu; Jing Zhao; et al. (Toxicology and Applied Pharmacology, 2025)

Pathogenic and beneficial microbial communities determine the shelf life of stored 'Fengtangli' plums - Yu-Ru Wang; Tomislav Cernava; Shi-Xian Zeng; Hong Chen; Feng-Quan Liu; Zheng-Qing Fu; Tao Zhou; Yong Wang; Jia Liu (Postharvest Biology and Technology, 2025)

Automated modal identification of offshore wind turbines via an uncertainty-quantified stochastic subspace method - Jing Song; Kang Zhou; Zhen-Ru Shu; Xiao-Ying Cai; Ming-Gang Duan (Ocean Engineering, 2025)

Soot characterization of n-dodecane combustion in multi-jet premixed flames: A multi-scale analysis - Xiao-Hong Gui; Jiao-Jiao Wu; Wen-Jun Zhou; Ling-Nan Wu; Kai-Ru Jin; Wen-Jiao Wang; Zhen-Yu Tian (Fuel, 2025)

Unveiling the 3D Li2S nucleation mechanism through ultra-small Ru engineering on MoS2 for high-efficiency Li S batteries - Mengjing Jin; Rui Wang; Shimin Wang; Ru Chen; Jiayue Li; Yanchun Wang; Renqian Tao; Guowen Sun; Jinyuan Zhou; Xiaojun Pan (Chemical Engineering Journal, 2025)

Isorhamnetin alleviates acute liver injury by blocking ferroptosis - Didi Liu; Yao Zeng; Tao Meng; Yi Ru; Xinru Zhou; Yun Huang; Wei Jiang; Xueting Lang; Ye Tao; Yi Huang (Chemical Engineering Journal, 2025)

A new norlignan and other compounds from Artemisia frigida Willd - Xin-Ya Dong; Ru-Ya Li; Hong-Xia Tang; Ya-Jie Li; Jun Chen; Jin-Guo Luo; Na Yu; Xiang-Wei Xu; Xu-Dong Zhou (Biochemical Systematics and Ecology, 2025)

Correction: The correlation of fibrinogen‑like protein‑1 expression with the progression and prognosis of hepatocellular carcinoma - Nanni Hua; Anxian Chen; Chen Yang; Hui Dong; Xianglei He; Guoqing Ru; Xiangmin Tong; Feifei Zhou; Shibing Wang (Molecular Biology Reports, 2025)

GNF-5837 attenuates acute liver injury by inhibiting oxidative stress - Xinru Zhou; Xianyu Luo; Qian Huang; Yi Ru; Didi Liu; Maoyuan Linghu; Yi Huang (Molecular Biology Reports, 2025)

Low-intensity pulsed ultrasound promotes proliferation and differentiation of neural stem cells to enhance spinal cord injury recovery - Ye-Hui Liao; Min-Hao Tian; Wen-Yang Zhou; Bao-Qiang He; Chao Tang; Qiang Tang; Ru-Pei Ye; De-Jun Zhong (Molecular Biology Reports, 2025)

Schwertmannite maintains effective stabilization of arsenic in flooded paddy soil: Insights from a two-season rice experiment and underlying mechanisms - Ru Wang; Yang Song; Yinglin Guo; Nan Ge; Xiaomeng Wang; Lixiang Zhou; Guanyu Zheng (Journal of Hazardous Materials, 2025)

Effects of EGCG/TGase on the physicochemical properties and in vitro dynamic digestion characteristics of water-saving rinsed surimi gels - Qin Yang; Weixia Zhou; Die Hu; Chuan Li; Lu Zhang; Yongqiang Zhao; Shengbi Zou; Ru Liu; Youming Liu; Jianhua Rong; Shanbai Xiong; Yang Hu (Food Chemistry, 2025)

Insights into cell wall metabolism and remodeling process of postharvest Coprinus comatus fruiting body - Yilong Zou; Yaru Zhang; Ru Li; Huabin Zhou; Hang Qu; Hailong Yang (Food Chemistry, 2025)

AO168=O at environmentally relevant concentrations induces reproductive toxicity by causing germline apoptosis and cell cycle arrest in Caenorhabditis elegans - Yuxing Wang; Luyao Gu; Simin Li; Ru Liu; Tong Meng; Yue Yu; Rong Ye; Houhu Zhang; Rong Zhou; Yuanqing Bu (Environmental Research, 2025)

Novel negative-zero-positive Poisson's ratio graded mechanical metamaterials for enhanced energy absorption: Performance investigation and design optimization - Yuze Nian; Yi-Qing Ni; Mehmet Avcar; Ru Yue; Kai Zhou (Engineering Structures, 2025)

Bridging photometric parameters and emotional well-being: validating the atmosphere perception scale to optimize illuminance and CCT interactions in occupational lighting - Yun Li; Jing Zhang; Jiaying Li; Siyu Li; Qingwei Chen; Taotao Ru; Guofu Zhou (Building and Environment, 2025)

Inhibition of the NLR pathway alleviates MAPK1 mutation-driven proliferation and differentiation deficits and enhanced apoptosis in P19 cells - Tingying Lei; Lei Liu; Fei Guo; Ru Li; Li Zhen; Fang Fu; Min Pan; Jin Han; Hang Zhou; Chunling Ma; Ruibin Huang; Xinyi Zhao; et al. (Tissue and Cell, 2025)

Nano architectonics via in situ growth of MIL-101(Fe) on modified sugarcane bagasse for selective capture of glyphosate from aqueous solution - Ru-yi Zhou; Ming-hua Liu; Yun Xiao; Yu Qin; Bo Zuo; Muhammad Akhtar Abbas; Jun-xia Yu; Xiao-di Li; Yue-fei Zhang; Ru-an Chi (Journal of Environmental Chemical Engineering, 2025)

Sequential fermentation with Kluyveromyces marxianus and yogurt starter cultures produces stirred fermented milk with reduced lactose and enhanced natural flavor - Yu-Ting Feng; Yan-Ru Zhou; Chang-Cheng Li; Shu-Jun Guo; Zhen-Peng Gao; Chun-Feng Guo (Innovative Food Science & Emerging Technologies, 2025)

Potassium isotopic equilibrium fractionation induced by clay adsorption and incorporation: A density functional theory study - Yin-Chuan Li; Hao-Long Li; Hai-Zhen Wei; Martin R. Palmer; Yong-Hui Li; Ya-Ru Zhou (Geochimica et Cosmochimica Acta, 2025)

Molecular epidemiology and phylogenetic analysis of Echinococcus spp. in the Qinghai-Tibetan Plateau: unraveling genetic evolution in a high-risk region for echinococcosis - Guoyan Zhou; Zhi Li; Xueyong Zhang; Ru Meng; Xiuying Shen; Zhen Zhang; Fuyun Chen; Hong Duo; Yong Fu (Veterinary Research Communications, 2025)

Tongxinluo alleviates myocardial ischemia–reperfusion injury by inhibiting the pyroptosis of endothelial cells via the NLRP3/Caspase-1/GSDMD signaling pathway - Xuan Wu; Yun-long Hou; Tong-xing Wang; Li-ping Chang; Hong-ru Zhou; Ming-ye Wang; Yi-ling Wu (Journal of Molecular Histology, 2025)

Genetic burden and multidimensional predictors in prenatal diagnosis of fetal congenital diaphragmatic hernia - Ruibin Huang; Fang Fu; Shanshan Mei; Liyuan Liu; Wei Zhong; Jin Han; Qiuxia Yu; Hang Zhou; Chunling Ma; Li Zhen; Min Pan; Qiong Deng; et al. (Human Genetics, 2025)

Subsurface organic ameliorant is beneficial in reducing inorganic carbon loss and improving carbon sequestration in saline soils - Ru Yu; Jiashen Song; Jie Zhou; Fangdi Chang; Xiaobin Li; Jing Wang; Haoruo Li; Xia Zhang; Hua Zhang; Yuexin Zhang; Hongyuan Zhang; Yuyi Li (Applied Soil Ecology, 2025)

Green manure roots return drives saline-alkali soil organic carbon accumulation via microbial necromass formation - Fangdi Chang; Hongyuan Zhang; Peiyi Zhao; Na Zhao; Jiashen Song; Ru Yu; Jing Wang; Xiquan Wang; Dongxun Han; Xiaodong Liu; Jie Zhou; Yuyi Li (Soil and Tillage Research, 2025)

Arabidopsis HSFA1b functions as a heat sensor inhibiting OST1-mediated stomatal closure through its adenylate-cyclase activity - Yu Zhang; Ru-Feng Song; Xiao-Yu Hu; Hui Zhou; Wei Wang; Junli Zhang; Xin Zhang; Liu-Mei Li; Su-Ting Wang; Yuwei Song; Fuyou Xiang; Jingjing Xing; et al. (Molecular Plant, 2025)

Comparison of hydroxylated flavonoids and their interaction with protein-based carriers - Zhi-Yuan Yang; Shan-Dan Zhao; Yu-Ru Wu; Qian Zhou; Wei Wang; Yi-Bin Zhou; Kang Liu (Food Chemistry, 2025)

Multispectral analysis and molecular docking simulation of the inhibition mechanism of dietary anthocyanins on acetylcholinesterase - Nuo Wang; Min Zhao; Yue Li; Hao-Yu Xue; Xu Si; Chi Shu; Ying Zhou; Bao-Ru Yang; Sergey S. Makarov; Anton I. Chudetsky; Liang Wang; Ying He; et al. (Food Bioscience, 2025)

L-Cysteine-promoted semi‑hydrogenation of alkynes over Pd nanoparticles-encapsulated hollow porous silica nanospheres - Lei Wang; Qianqian Zhou; Ru Hu; Xiaomeng Ren; Shenghu Zhou (Chemical Engineering Journal, 2025)

An ultrasound-visualized methionine partitioning nano-modulator for enhanced immunotherapy against anti-PD-1 resistant tumors - Yingying Zhao; Beibei Zhang; Shaobo Duan; Yaqiong Li; Yuzhou Wang; Yongchao Wang; Juan Zhang; Rong Huang; Ru Jiang; Rui Zhang; Qi Zhou; Linlin Zhang; et al. (Chemical Engineering Journal, 2025)

Transcriptome Profiling of the Primary and Crown Root in Response to Nitrate in Foxtail Millet (Setaria italica) - Xueting Kang; Jian-Hong Hao; Jiayi Chen; Xuan Zhou; Dan-Ying Chen; Rui Zhao; Ru Meng; Shuqi Dong; Xiangyang Yuan; Xiaorui Li; Lulu Gao; Guanghui Yang; et al. (Journal of Plant Growth Regulation, 2025)

Responses of plant community drought resistance and resilience to warming and nitrogen addition vary with recurrent droughts in a semi-arid grassland - Haidao Wang; Jian Song; Yongge Fan; Jianyang Xia; Lin Jiang; Qingshan Zhang; Heng Li; Jingyi Ru; Jiayin Feng; Lingjie Kong; Jiajun Zhang; Xueli Qiu; et al. (Agriculture, Ecosystems & Environment, 2025)

Orchard variable rate spraying method and experimental study based on multidimensional prescription maps - Chenming Hu; Yu Ru; Shuping Fang; Zifan Rong; Hongping Zhou; Xianghai Yan; Mengnan Liu (Computers and Electronics in Agriculture, 2025)

Incidence of respiratory diseases associated with per- and polyfluoroalkyl substances (PFAS) in PM2.5: New evidence from a population-based survey of Pearl River Delta (PRD), China - Lu-Yin Wu; Wan-Ting He; Mohammed Zeeshan; Yang Zhou; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Kun Zhao; Wen-Wen Bao; Li-Zi Lin; Zhao-Huan Gui; et al. (Journal of Hazardous Materials, 2025)

The heading stage: A critical period for schwertmannite in reducing arsenic accumulation in rice (Oryza sativa L.) - Yan Dong; Jiawei Yang; Ru Wang; Bo Zhou; Mingjiang Zhang; Guanyu Zheng; Lixiang Zhou (Journal of Environmental Sciences, 2025)

Thermophilic degradation of sulfamethazine by Geobacillus sp. S-07: pathway and mechanism - Ting Pan; Yan-Yan Zhou; Xu Huang; Jian-Xin Xu; Xiao-Yu Guo; Jian-Qiang Su; Hu Li; Xiao-Ru Yang (Environmental Research, 2025)

Transfer patterns of human blood to follicular fluid of per- and polyfluoroalkyl substances with distinct molecular structures and physico-chemical properties - Yun-Ting Zhang; Michael S. Bloom; Yang Zhou; Saif Ur Rehman; Chu Chu; Kun Zhao; Biao Yin; Zhong Lin; Yuan-Yuan Fan; Li-Zi Lin; Ru-Qing Liu; Weihong Tan; et al. (Journal of Hazardous Materials, 2025)

Experimental evidence for viral impact on microbial community, nitrification, and denitrification in an agriculture soil - Hu Li; Sha Zhao; Meng-Ke Gao; Yanyan Zhou; Bo Xu; Le-Yang Yang; Xiao-Ru Yang; Jian-Qiang Su (Journal of Hazardous Materials, 2025)

Floated Bi4Ti3O12@MoS2 p-n heterojunction anti-fouling hydrogels for efficient seawater purification - Ying Liu; Bingyan Ni; Ruotong Ru; Linlin Zhang; Hongfei Sun; Jianjun Liao; Cheng Li; Dexin Wang; Xiaodong Zhang; Wei Zhou (Journal of Environmental Chemical Engineering, 2025)

Co-encapsulation and stability evaluation of myricetin and epicatechin in the oxidized starch-coated edible dock protein hydrogels - Si-Qi Li; Zhi-Yuan Yang; Ming Yang; Wei Wang; Yu-Ru Wu; Yi-Bin Zhou; Kang Liu (Food Hydrocolloids, 2025)

High-performance multi-particle color electrophoretic display: A novel dual-charged particle strategy - Yue Zhang; Debo Zeng; Junjie He; Hailiang Sheng; Tao Zhou; Jintao Shi; Lisha Peng; Xinzao Wu; Bo-Ru Yang (Chemical Engineering Journal, 2025)

Holocene hydroclimatic changes inferred from a mountainous lake sedimentary record on the southeastern Tibetan Plateau - Jianchao Zhou; Jinglu Wu; Ru Guo; Ming Ji (International Journal of Earth Sciences, 2025)

Functional analysis of Ophraella communa Lesage OcomOBP11 in recognition of Ambrosia artemisiifolia L. volatiles - Yang Yue; Chao Ma; Yan Zhang; Wei-hua Ma; Jing-jing Wang; Zhen-ya Tian; Guang-mei Chen; Ru-wen Li; Jin-hua Li; Jing-fang Yang; Zhong-shi Zhou (Pesticide Biochemistry and Physiology, 2025)

Calculation and analysis of wave loads and hydrodynamic coefficients on submerged floating tunnels with various cross-sections - Hong-Fei Mao; Wei-Jiang Zheng; Qin-Ru Yang; Zhong-Bing Zhou; Zheng-Lin Tian; Long Han; Guang-Lin Wu; Jin-Bo Lin (Ocean Engineering, 2025)

Novel screening of molecular markers reveals genetic basis for heterosis in hybrids from red crucian carp and white crucian carp - He Zhang; Ru Li; Yun Zeng; Jun Wang; Zhizhi Liu; Yi Zhou; Chenghui Wang; Dong Liu (Aquaculture, 2025)

Aberrance of GAP43/p-GAP43 Closely Associates with the Pathology of Neuron Loss in Prion-Infected Rodent Models - Xiao-Xi Jia; Cao Chen; Chao Hu; Yue-Zhang Wu; Zhi-Yue Chao; Jia-Feng Zeng; Ru-Han A.; Dong-Hua Zhou; Yuan Wang; Wei-Wei Zhang; Kang Xiao; Li-Ping Gao; et al. (Molecular Neurobiology, 2025)

Leveraging Deep Learning to Extract Raindrop Size Gamma Distribution Parameters from Wind Profile Radar Data - Yu Huang; Zhiqun Hu; Lin Li; Ru Zhou; Xu Lu; Mengyu Huang (Journal of Meteorological Research, 2025)

Location optimization of unmanned aerial vehicle (UAV) drone port for coastal zone management: The case of Guangdong coastal zone in China - Jia Sun; Sijing Shu; Hongda Hu; Yingbin Deng; Zhao Li; Shengnan Zhou; Yue Liu; Minwen Dang; Wumeng Huang; Zhiwei Hou; Xiaoling Yin; Ru Zhang; et al. (Ocean & Coastal Management, 2025)

Urinary biomarkers of drinking water disinfection byproducts in relation to blood-based liver function parameters among reproductive-aged Chinese women - Ping-Ping Gui; Yan-Ling Deng; Min Zhang; Yu Miao; Peng-Hui Liu; Jia-Yue Zeng; Yang Wu; Cheng-Ru Li; Xiao-Ying Liu; Yang-Juan Li; Jin-Qin Zhu; A-Xue Liu; et al. (Science of The Total Environment, 2025)

The Arabidopsis heterotrimeric G protein α subunit binds to and inhibits the inward rectifying potassium channel KAT1 - Jiang-Fan Guo; Hui Zhou; Zhuo-Ran Hu; Ya-Lan Yang; Wen-Bin Wang; Yan-Ru Zhang; Xue Li; Nuerkaimaier Mulati; Ying-Xin Li; Lu Wu; Yu Long; Jun-Min He (Plant Science, 2025)

Microbiological, physicochemical, textural, and rheological properties of fermented soymilk produced with Enterococcus faecium and Lactiplantibacillus plantarum - Chang-Cheng Li; Shu-Jun Guo; Yu-Ting Feng; Yan-Ru Zhou; Yue Li; Zhen-Peng Gao; Chun-Feng Guo (Food Chemistry, 2025)

Synergistic toxicity of cadmium and triadimefon on the microbiota and health of Rana dybowskii tadpoles - Xiao-yun Han; Peng Guo; Qiu-ru Fan; Qing-bo Zhou; Ming-da Xu; Xin-zhou Long; Li-yong Cui; Qing Tong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Drug–drug interaction of phenytoin sodium and methylprednisolone on voriconazole: a population pharmacokinetic model in children with thalassemia undergoing allogeneic hematopoietic stem cell transplantation - Yun Wu; Lu-lu Niu; Ya-yun Ling; Si-ru Zhou; Tian-min Huang; Jian-ying Qi; Dong-ni Wu; Rong-da Cai; Ting-qing Wu; Yang Xiao; Taotao Liu (European Journal of Clinical Pharmacology, 2025)

Thresholding Dolphin Whistles Based on Signal Correlation and Impulsive Noise Features Under Stationary Wavelet Transform - Xiang Zhou; Ru Wu; Wen Chen; Meiling Dai; Peibin Zhu; Xiaomei Xu (Journal of Marine Science and Engineering, 2025)
The time–frequency characteristics of dolphin whistle signals under diverse ecological conditions and during environmental changes are key research topics that focus on the adaptive and response mechanisms of dolphins to the marine environment. To enhance the quality and utilization of passive acoustic monitoring (PAM) recorded dolphin whistles, the challenges faced by current wavelet thresholding methods in achieving precise threshold denoising under low signal-to-noise ratio (SNR) are confronted. This paper presents a thresholding denoising method based on stationary wavelet transform (SWT), utilizing suppression impulsive and autocorrelation function (SI-ACF) to select precise thresholds. This method introduces a denoising metric ρ, based on the correlation of whistle signals, which facilitates precise threshold estimation under low SNR without requiring prior information. Additionally, it exploits the high amplitude and broadband characteristics of impulsive noise, and utilizes the multi-resolution information of the wavelet domain to remove impulsive noise through a multi-level sliding window approach. The SI-ACF method was validated using both simulated and real whistle datasets. Simulated signals were employed to evaluate the method’s denoising performance under three types of typical underwater noise. Real whistles were used to confirm its applicability in real scenarios. The test results show the SI-ACF method effectively eliminates noise, improves whistle signal spectrogram visualization, and enhances the accuracy of automated whistle detection, highlighting its potential for whistle signal preprocessing under low SNR.

Knockdown and insecticidal activities of pyrethrum, dimefluthrin and meperfluthrin against Aedes aegypti and Aedes albopictus - Mengli Chen; Ru Yan; Zhanyi Xu; Qiaoling Zhou; Yuyan Wu (International Journal of Tropical Insect Science, 2025)

Water-rock interaction-induced degradation of Jinping marble in in-situ environments: A multi-scale analysis of mechanical behavior - Chendi Lou; Ru Zhang; Zetian Zhang; Li Ren; Jing Xie; Kun Xiao; Mingchuan Li; Jifang Zhou; Anlin Zhang (International Journal of Rock Mechanics and Mining Sciences, 2025)

Equilibrium boron isotope fractionation during kaolinite adsorption and applications to chemical weathering processes - Yin-Chuan Li; Ya-Ru Zhou; Hai-Zhen Wei; Martin R. Palmer; Fa-Yang Guo; Yong-Hui Li; Yong-An Qi; Da-Ping Xia (Geochimica et Cosmochimica Acta, 2025)

Ultra-low energy wastewater remediation: Excellent properties of smart adsorption membranes - Yun-Hao Xia; Ying-Ying Gui; Jia-Hua Zhou; Gui-E Chen; Zhe-Ru Shi; Zhen-Liang Xu (Chemical Engineering Journal, 2025)

Discovering Phlebia acerina for efficient degradation of bisphenol S and insights into its degradation mechanism - Mingdong Chang; Ji-Hang Jiang; Jianqiao Wang; Ru Yin; Qiaoyu Li; NaNa Wang; Pengfei Xiao; Li-Wei Zhou; Tangfu Xiao (Bioresource Technology, 2025)

Impact of carbon/nitrogen ratio on sequencing batch biofilm reactors initiated with different seed sludges for treating actual mariculture effluents - Xiao-Yan Fan; Shi-Long Zhou; Yanling Yang; Shen-Bin Cao; Yue Niu; Meng-Yuan Zheng; Jun-Ru Zhao (Bioresource Technology, 2025)

Persistence evaluation of fecal pollution indicators in dewatered sludge and dewatering filtrate of municipal sewage sludge: The impacts of ambient temperature and conditioning treatments - Yuhang Wang; Hua Li; Wenhao Fang; Ru Wang; Xinxin Wang; Xiaomeng Wang; Guanyu Zheng; Lixiang Zhou (Water Research, 2025)

Amorphous Solid Dispersions of Glycyrrhetinic Acid: Using Soluplus, PVP, and PVPVA as the Polymer Matrix to Enhance Solubility, Bioavailability, and Stability - Meng-yu Zhao; Xian-bao Shi; Jin-hua Chang; Ru-xing Wang; Jian-yu Zhou; Pei Liu (AAPS PharmSciTech, 2024)

Phase transformation of schwertmannite changes microbial iron and sulfate-reducing processes in flooded paddy soil and decreases arsenic accumulation in rice (Oryza sativa L.) - Ru Wang; Xinxin Wang; Hua Li; Xiaomeng Wang; Zengping Ning; Chengshuai Liu; Lixiang Zhou; Guanyu Zheng (Soil Biology and Biochemistry, 2024)

Promotion of antibiotic-resistant genes dissemination by the micro/nanoplastics in the gut of snail Achatina fulica - Yan-Mei Da; Xiao-Ru Yang; Ming-Jun Li; Shun-Shun Li; Ze-Ping Gao; Ying Zhang; Jian-Qiang Su; Guo-Wei Zhou (Science of The Total Environment, 2024)

Integrative models for environmental forecasting of phthalate migration from microplastics in aquaculture environments - Shan Zhong; Ruiyue Li; Yaowen Tian; Zengxian Wei; Lishan Zhang; Yan Chen; Ruyue Zhou; Qian Zhang; Xuan Ru (Journal of Hazardous Materials, 2024)

Bacterial necromass as the main source of organic matter in saline soils - Jiashen Song; Hongyuan Zhang; Bahar Razavi; Fangdi Chang; Ru Yu; Xia Zhang; Jing Wang; Jie Zhou; Yuyi Li; Yakov Kuzyakov (Journal of Environmental Management, 2024)

The formation of protein coronas and its effect on the quercetin-edible dock protein nanoparticles - Yu-Ru Wu; Qian Zhou; Jing Li; Wei Wang; Yi-Bin Zhou; Kang Liu (Food Hydrocolloids, 2024)

Advanced growing-season precipitation peak promotes soil nitrogen mineralization in a semi-arid grassland - Jiayin Feng; Xiaojing Yue; Benqing Li; Jingyi Ru; Zhenxing Zhou; Lingjie Kong; Jiajun Zhang; Jiaxin Zhou; Guilin Zhou; Wenjing Ma; Yaru Lyu; Jian Song; et al. (CATENA, 2024)

PRDX1 Interfering Peptide Disrupts Amino Acids 70–90 of PRDX1 to Inhibit the TLR4/NF-κB Signaling Pathway and Attenuate Neuroinflammation and Ischemic Brain Injury - Xiang-Yu Ma; Cheng-yu Qi; Xing-yi Xu; Hui Li; Chang-Dong Liu; Xiang-Ru Wen; Yan-Yan Fu; Yan Liu; Jia Liang; Cheng-Yu Huang; Dan-Dan Li; Yan Li; et al. (Molecular Neurobiology, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

A ratiometric fluorescent probe based on UiO-66-TCPP for selective and visual detection of quercetin in food - Yiran Wang; Xiaolong Sun; Yufeng Zhou; Jiachen Liu; Huayue Zhu; Ru Jiang; Yingjie Miao; Yongqian Fu (Food Chemistry, 2024)

Most appropriate nozzle of six-rotor UAV for prescribed spraying liquid in tea plantation under effects of downwash flow structure in hover - Nai-Hong Hu; Wen-Xuan Zhou; Lin Zhu; Yan-Cheng Li; Xin-Yu Xie; Ru-Yan Hou; Cheng-Long Yin (Crop Protection, 2024)

Assessing the role of urban green infrastructure in mitigating summertime Urban Heat Island (UHI) effect in metropolitan Shanghai, China - Hao Zhang; Meng-yuan Kang; Zhen-ru Guan; Rui Zhou; Ai-lian Zhao; Wen-jia Wu; Hao-rong Yang (Sustainable Cities and Society, 2024)

ESR chronology of the Quaternary sedimentary sequence of the Shinaimiao borehole in Hebi City, Henan Province, China - Hao Ji; Zhong-shan Shen; Chun-Ru Liu; Xiong-Nan Huang; Xiao-Ping Yang; Chuan-Yi Wei; Xin-Xiu Li; Qing Zhou; Gong-Ming Yin (Quaternary Geochronology, 2024)

Long-term ambient ozone exposure and childhood asthma, rhinitis, eczema, and conjunctivitis: A multi-city study in China - Zhao-Huan Gui; Zhan-Yu Guo; Yang Zhou; Shyamali Dharmage; Lidia Morawska; Joachim Heinrich; Zhang-Kai Cheng; Hui Gan; Zhi-Wei Lin; Dong-Ying Zhang; Jing-Wen Huang; Li-Zi Lin; et al. (Journal of Hazardous Materials, 2024)

The construction of yeast β-glucan coated-edible dock protein nanomicelles for the encapsulation and sustained release of apigenin - Qian Zhou; Xiao-Jie Wang; Yu-Ru Wu; Weinan Zhang; Jing Li; Wei Wang; Ying-Nan Liu; Zhen-Yu Yu; Ming-Ming Zheng; Yi-Bin Zhou; Kang Liu (Journal of Food Engineering, 2024)

A bifunctional thiobenzamide additive for improvement of cathode kinetics and anode stability in lithium-sulfur batteries - Junpeng Rao; Tong Yu; Youshuang Zhou; Ru Xiao; Yaozu Wang; Zhuoyan Qu; Dean Shi; Zhenhua Sun; Feng Li (Chemical Engineering Journal, 2024)

Lowering Schottky barrier in MoC-based cocatalyst via heteroatoms tunning for enhanced photocatalytic hydrogen evolution - Ru-zhou Miao; Yu-long Bao; Guang Yang; Ying-jie Sun; Xiao-jing Wang; Jun Zhao; Hui-ying Mu; Fa-tang Li (Chemical Engineering Journal, 2024)

High-transmittance, fast-response, colored smart windows based on lateral-driving electrophoretic display - Yue Zhang; Jinglan Yang; Feng Xiong; Debo Zeng; Tao Zhou; Jintao Shi; Bo-Ru Yang (Chemical Engineering Journal, 2024)

Water–Rock reactions in the acid leaching of Uranium: Hydrochemical characteristics and reaction mechanisms - Bing Wang; Yue Luo; Xun Li; Ya–zhou Liu; Chang–rui Xu; Yu–xiu Zheng; Yan–hong Zhang; Yi–ru Zhou (Journal of Hydrology, 2024)

Cross-instar larval identification leads divergent decision on pest management: An example from white grubs on peanuts - Wen-Jun Cao; Yi-Nuo Chen; Ru-Jun Zhou; Lu Jiang (Journal of Asia-Pacific Entomology, 2024)

Enhancing vitamin D3 bioaccessibility: Unveiling hydrophobic interactions in soybean protein isolate and vitamin D3 binding via an infant in vitro digestion model - Jia-Rong Huang; Jing-Ru Song; Wan-Shuang Cai; Zhen-Wen Shao; Da-Yong Zhou; Liang Song (Food Chemistry, 2024)

Phase transformation of schwertmannite in paddy soil under different water management regimes and its impact on the migration of arsenic in soil - Ru Wang; Jing Zhuang; Shufan Chen; Hua Li; Xiaomeng Wang; Zengping Ning; Chengshuai Liu; Guanyu Zheng; Lixiang Zhou (Environmental Pollution, 2024)

Glycine to valine substitution in the short intracellular linkers of domain II enhances I1011M-mediated sodium channel resistance to Type I pyrethroids, but not Type II pyrethroids - Mengli Chen; Xiangyi Zhou; Guoxing Chen; Zhanyi Xu; Jiali Qian; Guonian Zhu; Ru Yan (Pesticide Biochemistry and Physiology, 2024)

Rapid, sensitive, and visual detection of pseudorabies virus with an RPA-CRISPR/EsCas13d-based dual-readout portable platform - Dong You; Tong Xu; Bing-Zhou Huang; Fang Wu; Li-Shuang Deng; Zhe-Yan Liu; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; Yuan-Cheng Zhou; Si-Yuan Lai; et al. (Analytica Chimica Acta, 2024)

Novel pyrrolidine-alkylamino-substituted dicyanoisophorone derivatives as near-infrared fluorescence probe for imaging β-amyloid in vitro and in vivo - Hui Zhou; Jihang Zhai; Huiyuan Gong; Ru Fang; Yongmei Zhao; Wen Luo (Analytica Chimica Acta, 2024)

Metabolomics for tea authentication and fraud detection: Recent applications and future directions - Hui Ru Tan; Weibiao Zhou (Trends in Food Science & Technology, 2024)

Electronic-rich large conjugated molecules dispersing through ionic liquid solution process for fluorescent detection of iodine gas - Yue-Ru Zhou; Shuang-Long Wang; Lei Zhang; Jie Fu; Ling He; Guo-Hong Tao (Chemical Engineering Journal, 2024)

SIRT3-Mediated Deacetylation of SDHA Rescues Mitochondrial Bioenergetics Contributing to Neuroprotection in Rotenone-Induced PD Models - Yanhua Shen; Xueting Wang; Nan Nan; Xiaolong Fu; Ru Zeng; Yonggang Yang; Siting Xian; Jingshan Shi; Qin Wu; Shaoyu Zhou (Molecular Neurobiology, 2024)

Path tracking control for brake-steering tracked vehicles based on an improved pure pursuit algorithm - Chenming Hu; Yu Ru; Xianzhe Li; Shuping Fang; Hongping Zhou; Xianghai Yan; Mengnan Liu; Rong Xie (Biosystems Engineering, 2024)

Differences among Lactiplantibacillus plantarum strains isolated from different fermented foods in their potential cholesterol-lowering properties - Shu-Jun Guo; Chang-Cheng Li; Yu-Ting Feng; Yan-Ru Zhou; Bin Liu; Zhen-Peng Gao; Chun-Feng Guo (Food Bioscience, 2024)

Inorganic carbon accumulation in saline soils via modification effects of organic amendments on dissolved ions and enzymes activities - Jiashen Song; Hongyuan Zhang; Kazem Zamanian; Fangdi Chang; Ru Yu; Jing Wang; Jie Zhou; Yuyi Li (CATENA, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Aconitum coreanum and processed products on its base prevent stroke via the PI3K/Akt and KEAP1/NRF2 in the in vivo study - Wan-ting Zeng; Li-ting Zhou; Ru Jia; Yue Liu; Qian Cai; Yang Qu (Metabolic Brain Disease, 2024)

Pivotal role of intracellular oxidation by HOCl in simultaneously removing antibiotic resistance genes and enhancing dewaterability during conditioning of sewage sludge using Fe2+/Ca(ClO)2 - Xinxin Wang; Yu Lu; Yiwen Yan; Ru Wang; Yuhang Wang; Hua Li; Lixiang Zhou; Guanyu Zheng; Yifeng Zhang (Water Research, 2024)

Blue-light irradiation induced partial nitrification - Ru Zheng; Yiming Feng; Lingrui Kong; Xiaogang Wu; Jianhang Zhou; Liguo Zhang; Sitong Liu (Water Research, 2024)

BDNF mimetics recover palmitic acid-induced injury in cardiomyocytes by ameliorating Akt-dependent mitochondrial impairments - Man-Ru Zhang; Bang-Yun Zuo; Yu-Chen Song; Dan-Dan Guo; Qing-Liu Li; Jin-Xiu Lyu; Hua Zhu; Jing Zhao; Peng-Zhou Hang (Toxicology and Applied Pharmacology, 2024)

Downhole detection of gas kick using low-frequency elastic wave: Multiphysics modeling and its implications - Zizhen Wang; Ru Zhao; Yanbin Zang; Weidong Zhou; Guanlin Chen; Rui Zhang (Gas Science and Engineering, 2024)

A novel ionic-liquid-mediated covalent organic framework as a strong electrophile for high-performance iodine removal - Jie Fu; Jia-Ying Liu; Yue-Ru Zhou; Lei Zhang; Shuang-Long Wang; Song Qin; Maohong Fan; Guo-Hong Tao; Ling He (Chemical Engineering Journal, 2024)

Efficient removal of size-fractionated antibiotic resistance genes (ARGs) in WWTPs secondary effluent by vacuum ultraviolet (VUV) activated potassium peroxymonosulfate (PMS) - Xiao-Yan Fan; Shi-Long Xu; Xing Li; Zhi-Wei Zhou; Yu-Xi Gao; Jun-Ru Zhao; Zhong-Xing Zhang (Chemical Engineering Journal, 2024)

Experiments and CFD simulation of downwash airflow and fog distribution discharged from a single-rotor UAV fitted with a pulse-jet thermal fogging machine - Jian Zhang; Qing Chen; Jian Liu; Yan Wang; Hongping Zhou; Fengbo Yang; Yu Ru (Biosystems Engineering, 2024)

Opportunist ant species dominate metropolitan microhabitats: Evidence from the eastern margin of the Qinghai-Tibetan plateau - Ru-Yi Yin; Xin-Yu Luo; Xiang-Qin Huang; Zi-Xuan Zhao; Chris Newman; Yi Luo; Zhao-Min Zhou (Soil Biology and Biochemistry, 2024)

Nitrogen addition does not alter symmetric responses of soil respiration to changing precipitation in a semi-arid grassland - Lingjie Kong; Jian Song; Jingyi Ru; Jiayin Feng; Jiawei Hou; Xueke Wang; Qingshan Zhang; Haidao Wang; Xiaojing Yue; Zhenxing Zhou; Dasheng Sun; Jiajia Zhang; et al. (Science of The Total Environment, 2024)

Cultivating edible bio-inks: Elevating 3D printing with medium-internal-phase emulsion gel incorporating soybean protein isolate microgel particles - Jing-ru Song; Jia-rong Huang; Si-xu Ren; Hong-ze Zheng; Da-yong Zhou; Liang Song (Food Hydrocolloids, 2024)

Carbon tax and low-carbon credit: Which policy is more beneficial to the capital-constrained manufacturer's remanufacturing activities? - Zhan-Jie Wang; Ru-Fu Zhou; Yong-Feng Ma; Yong-Jian Wang (Environmental Research, 2024)

Sea-Surface Small Target Detection Based on Improved Markov Transition Fields - Ru Ye; Hongyan Xing; Xing Zhou (Journal of Marine Science and Engineering, 2024)
Addressing the limitations of manually extracting features from small maritime target signals, this paper explores Markov transition fields and convolutional neural networks, proposing a detection method for small targets based on an improved Markov transition field. Initially, the raw data undergo a Fourier transform, feature fusion is performed on the series, and a spectrogram is generated using Markov transition fields to extract radar data features from both the time domain and frequency domain, providing a more comprehensive data representation for the detector. Then, the InceptionResnetV2 network is employed as a classifier, setting decision thresholds based on the softmax layer’s output, thus achieving controllable false alarms in the detection of small maritime targets. Additionally, transfer learning is introduced to address the issue of sample imbalance. The IPIX dataset is used for experimental verification. The experimental results show that the proposed detection method can deeply mine the differences between targets and the maritime clutter background, demonstrating superior detection performance. When the observation time is set to 1.024 s, the IMIRV2 detector performs best. Cross-validation with different data preprocessing methods and classification models reveals a significant advantage in the performance of the IMIRV2 detector, especially at low signal-to-noise ratios. Finally, a comparison with the performance of existing detectors indicates that the proposed method offers certain improvements.

Experimental study of the influence factors of the droplet size of rotary nozzles during manned helicopter spraying operations - Yu Ru; Shuping Fang; Jiangkun Xue; Chenming Hu; Jie Zhou (Crop Protection, 2024)

Conductive nanofiltration membranes via in situ PEDOT-polymerization for electro-assisted membrane fouling mitigation - Tian-Zhi Jia; Ru Feng; Chun Cui; Qian Chen; Levente Cseri; Rong-Fei Zhou; Gyorgy Szekely; Xue-Li Cao; Shi-Peng Sun (Water Research, 2024)

Subsurface organic amendment of a saline soil increases ecosystem multifunctionality and sunflower yield - Jiashen Song; Hongyuan Zhang; Fangdi Chang; Ru Yu; Jing Wang; Aiping Chen; Yang Xu; Yu Liu; Jie Zhou; Yuyi Li (Science of The Total Environment, 2024)

Communication mediated interaction between bacteria and microalgae advances photogranulation - Xiaogang Wu; Lingrui Kong; Yiming Feng; Ru Zheng; Jianhang Zhou; Jingqi Sun; Sitong Liu (Science of The Total Environment, 2024)

Enhancing phenology modeling through the integration of artificial light at night effects - Haoming Xia; Longxin Qiao; Yan Guo; Xutong Ru; Yaochen Qin; Yuyu Zhou; Chaoyang Wu (Remote Sensing of Environment, 2024)

Modification of polyacrylonitrile ultrafiltration membrane with acylase for enhanced biofouling control based on quorum quenching - Bingqian Hou; Xinyu Chen; Danni Wang; Ru Geng; Xiangtong Zhou; Xiang Xiao; Xinshan Rong; Zhiren Wu; Jing Wei (Journal of Water Process Engineering, 2024)

Relationship of single and co-exposure of per-and polyfluoroalkyl substances and their alternatives with uric acid: A community-based study in China - Li-Xia Liang; Li-Zi Lin; Mohammed Zeeshan; Yang Zhou; Yong-Xiang Tang; Chu Chu; Yun-Ting Zhang; Ru-Qing Liu; Wenru Feng; Guang-Hui Dong (Journal of Hazardous Materials, 2024)

6PPD-quinone exposure induces neuronal mitochondrial dysfunction to exacerbate Lewy neurites formation induced by α-synuclein preformed fibrils seeding - Jiacheng Fang; Xiaoxiao Wang; Guodong Cao; Fuyue Wang; Yi Ru; Bolun Wang; Yanhao Zhang; Doudou Zhang; Jie Yan; Ji Xu; Jing Ji; Fenfen Ji; et al. (Journal of Hazardous Materials, 2024)

Efficient synthesis of squalene by cytoplasmic-peroxisomal engineering and regulating lipid metabolism in Yarrowia lipolytica - Yang Ning; Mengsu Liu; Ziyun Ru; Weizhu Zeng; Song Liu; Jingwen Zhou (Bioresource Technology, 2024)

Integrated transcriptome and metabolome analysis revealed that HaMYB1 modulates anthocyanin accumulation to deepen sunflower flower color - Siqi Ma; Hanlin Zhou; Tingting Ren; Er-ru Yu; Bin Feng; Juying Wang; Chengsheng Zhang; Chao Zhou; Yiqiang Li (Plant Cell Reports, 2024)
Key message HanMYB1 was found to play positive roles in the modulation of anthocyanins metabolism based on the integrative analysis of different color cultivars and the related molecular genetic analyses. Abstract As a high value ornamental and edible crop with various colors, sunflowers ( Helianthus annuus L.) provide an ideal system to understand the formation of flower color. Anthocyanins are major pigments in higher plants, which is associated with development of flower colors and ability of oxidation resistance. Here, we performed an integrative analysis of the transcriptome and flavonoid metabolome in five sunflower cultivars with different flower colors. According to differentially expressed genes and differentially accumulated flavonoids, these cultivars could be grouped into yellow and red. The results showed that more anthocyanins were accumulated in the red group flowers, especially the chrysanthemin. Some anthocyanins biosynthesis-related genes like UFGT (UDP-glycose flavonoid glycosyltransferase) also expressed more in the red group flowers. A MYB transcriptional factor, HanMYB1, was found to play vital positive roles in the modulation of anthocyanins metabolism by the integrative analysis. Overexpressed HanMYB1 in tobacco could deepen the flower color, increase the accumulation of anthocyanins and directly active the express of UFGT genes. Our findings indicated that the MYB transcriptional factors provide new insight into the dynamic regulation of the anthocyanin biosynthesis in facilitating sunflower color formation and anthocyanin accumulation.

Ratiometric G-quadruplex/hemin DNAzymes with low-dosage associative substrates - Rong Lai; Xingli Zeng; Qiuda Xu; Ying Xu; Xueni Li; Yulu Ru; Yilin Wang; Dandan Wang; Xiaoshun Zhou; Yong Shao (Analytica Chimica Acta, 2024)

Long-term exposure to the mixture of phthalates induced male reproductive toxicity in rats and the alleviative effects of quercetin - Li-Lan Liu; Jun-Zhe Yue; Zhen-Yu Lu; Ru-Ya Deng; Can-Can Li; Ye-Na Yu; Wen-Jin Zhou; Min Lin; Hai-Tao Gao; Jiaming Liu; Ling-Zi Xia (Toxicology and Applied Pharmacology, 2024)

The application of nanopore targeted sequencing for pathogen diagnosis in bronchoalveolar lavage fluid of patients with pneumonia: a prospective multicenter study - Qinqing Lin; Yake Yao; Xi Li; Shanshan Zhang; Huimin Guo; Xiaolong Ma; Wenyu Chen; Chuhui Ru; Limin Wang; Bin Wang; Qiang Ma; Junfei Zhu; et al. (Infectious Diseases, 2024)

TAT-W61 peptide attenuates neuronal injury through blocking the binding of S100b to the V-domain of Rage during ischemic stroke - Jia Liang; Hui Li; Chang‑Dong Liu; Xiao‑Yan Zhou; Yan‑Yan Fu; Xiang-Yu Ma; Dan Liu; Yu-Ling Chen; Qian Feng; Zhen Zhang; Xiang-Ru Wen; Guang Zhu; et al. (Journal of Molecular Medicine, 2024)

Assessing production–living–ecological spaces and its urban–rural gradients in Xiangyang City, China: insights from land-use function symbiosis - Chao Liu; Qingke Yang; Fenghua Zhou; Ru Ai; Long Cheng (Environmental Science and Pollution Research, 2024)

A novel eco-friendly strategy for removing phenanthrene from groundwater: Synergism of nanobubbles and rhamnolipid - Wang Kai Tong; Chaomeng Dai; Jiajun Hu; Jixiang Li; Min-tian Gao; Xueji You; Xin Ru Feng; Zhi Li; Lang Zhou; Yalei Zhang; Xiaoying Lai; Long Kahon; et al. (Science of The Total Environment, 2024)

Soil microbial diversity and network complexity drive the ecosystem multifunctionality of temperate grasslands under changing precipitation - Changchun Zhai; Lili Han; Chao Xiong; Anhui Ge; Xiaojing Yue; Ying Li; Zhenxing Zhou; Jiayin Feng; Jingyi Ru; Jian Song; Lin Jiang; Yunfeng Yang; et al. (Science of The Total Environment, 2024)

Accelerated removal of naproxen in the iron-based peracetic acid activation system by chloride ions: Enhancement of reactive oxidative species via the formation of iron-chloride complexes - Si-Ying Yu; Yang Shi; Chuan-Shu He; Yu-Dan Dong; Si Sun; Ru-Yan Ning; Zhao-Kun Xiong; Peng Zhou; Heng Zhang; Bo Lai (Journal of Hazardous Materials, 2024)

Global, regional, and national burden of ischemic heart disease attributable to ambient PM2.5 from 1990 to 2019: An analysis for the global burden of disease study 2019 - Li-Hao Guo; Li-Zi Lin; Yang Zhou; Bin Jalaludin; Lidia Morawska; Shyamali C. Dharmage; Luke D. Knibbs; Guo-Feng Huang; Duo-Hong Chen; Huimin Ma; Meng Gao; Joachim Heinrich; et al. (Environmental Research, 2024)

High-strength ionic hydrogel constructed by metal-free physical crosslinking strategy for enhanced uranium extraction from seawater - Yuan-Hao Wang; Yu-Qin Xiang; Qian Huang; Xiao-Lan Yang; Shuang-Long Wang; Yue-Ru Zhou; Song Qin; Ling-Qiong Gou; Guo-Hong Tao; Ling He (Chemical Engineering Journal, 2024)

Comammox plays a functionally important role in the nitrification of rice paddy soil with different nitrogen fertilization levels - Kai Zhang; Hui-Feng Sun; You-Cai Kang; Ran Jiang; Yan-Ren Wang; Ru-Yi Zhang; Sheng-Nan Zhang; Yang-Yang Li; Peng Li; Fan Yang; Sheng Zhou; Zhe-Xue Quan (Applied Soil Ecology, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

A novel hydrangea-like magnetic composite Fe3O4@MnO2@ZIF-67 for efficient selective adsorption of Pd(II) from metallurgical wastewater - Xue Jiang; Yu Zhou; Haiou Chen; Ru Zhang; Junhui Yu; Shixiong Wang; Fengzhi Jiang; Huiping Bai; Xiangjun Yang (Chemosphere, 2023)

Burying straw interlayers decreases CO2 emissions in deep saline soil - Jiashen Song; Hongyuan Zhang; Leanne Peixoto; Fangdi Chang; Ru Yu; Xiquan Wang; Jing Wang; Jufeng Cao; Jie Zhou; Amit Kumar; Yuyi Li (Sustainable Production and Consumption, 2023)

Corrigendum to “Silica nanoparticles promote oxLDL-induced macrophage lipid accumulation and apoptosis via endoplasmic reticulum stress signaling” [Sci. Total Environ., 631-632 (2018): 570-579] - Caixia Guo; Ru Ma; Xiaoying Liu; Tian Chen; Yang Li; Yang Yu; Junchao Duan; Xianqing Zhou; Yanbo Li; Zhiwei Sun (Science of The Total Environment, 2023)

Topology optimization on periodic pile barriers considering material damping based on complex band diagrams - Peng Zhou; Shui Wan; Xiao Wang; Aiming Song; Ru Yue (Computers and Geotechnics, 2023)

Humic acid plus manure increases the soil carbon pool by inhibiting salinity and alleviating the microbial resource limitation in saline soils - Jiashen Song; Hongyuan Zhang; Fangdi Chang; Ru Yu; Xiangqian Zhang; Xiquan Wang; Weini Wang; Junmei Liu; Jie Zhou; Yuyi Li (CATENA, 2023)

Study on Creep Characteristics and Nonlinear Fractional-Order Damage Constitutive Model of Weakly Cemented Soft Rock - Wenkai Ru; Shanchao Hu; Aohui Zhou; Pingkuang Luo; Hao Gong; Chenxi Zhang; Xuedong Zhou (Rock Mechanics and Rock Engineering, 2023)

Urban greenspace types influence the microbial community assembly and antibiotic resistome more in the phyllosphere than in the soil - Xin-Rong Huang; Roy Neilson; Le-Yang Yang; Jing-Jun Deng; Shu-Yi-Dan Zhou; Hu Li; Yong-Guan Zhu; Xiao-Ru Yang (Chemosphere, 2023)

Maternal transfer of F-53B inhibited neurobehavior in zebrafish offspring larvae and potential mechanisms: Dopaminergic dysfunction, eye development defects and disrupted calcium homeostasis - Luyin Wu; Mohammed Zeeshan; Yao Dang; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Yuan-Yuan Fan; Ming-Kun Sun; Tao Yu; Yue Wen; et al. (Science of The Total Environment, 2023)

Efficient removal of impurities from phosphogypsum during preparation of α-hemihydrate gypsum - Qingjun Guan; Yulin Zhou; Weijian Yu; Ruihua Fan; Ying Sui; Yongjie Bu; Zhigang Yin; Ru-an Chi; Zhiyong Gao (Minerals Engineering, 2023)

Rethinking personal carbon trading (PCT) mechanism: A comprehensive review - Yun-En Tang; Ru Fan; Ang-Zu Cai; Le-Yi Wang; Rui-Min Lin; Xiang-Zhou Meng; Ling Chen; Ru Guo (Journal of Environmental Management, 2023)

Creep properties and energy evolution characteristics of weakly cemented rock under step loading - Shanchao Hu; Chenxi Zhang; Wenkai Ru; Jinming Han; Shihao Guo; Xuedong Zhou; Lei Yang (International Journal of Rock Mechanics and Mining Sciences, 2023)

Self-assembly and interaction mechanisms of edible dock protein and flavonoids regulated by the phenolic hydroxyl position - Qian Zhou; Xiao-Jie Wang; Jing Li; Yu-Ru Wu; Wei Wang; Zhen-Yu Yu; Ya-Qing Xiao; Ying-Nan Liu; Shi-Yi Li; Ming-Ming Zheng; Yi-Bin Zhou; Kang Liu (Food Chemistry, 2023)

Climate warming may accelerate apple phenology but lead to divergent dynamics in late-spring frost and poor pollination risks in main apple production regions of China - Xiaoya Ru; Jie Zhou; Kaiyuan Gong; Zhihao He; Zhanwu Dai; Meirong Li; Xinxin Feng; Qiang Yu; Hao Feng; Jianqiang He (European Journal of Agronomy, 2023)

Highly effective and selective recovery of Gd(III) from wastewater by defective MOFs-based ion-imprinted polymer: Performance and mechanism - Ming yang; Yuxin Zhou; Dandan Zhang; Fang Zhou; Hui Ning; Maoxia He; Ru-an Chi; Weiyan Yin (Chemical Engineering Journal, 2023)

Adult Kerion Celsi Caused by Trichophyton tonsurans Secondary to Black Dot Tinea Capitis - Qian-ru Ye; Yu-wu Luo; Xin Zhou; Qing-qing Li; Yu-mei Liu (Mycopathologia, 2023)
A 34-year-old female patient presented with hair loss due to black dot tinea capitis caused by Trichophyton tonsurans for 6 months. Hair loss progressed to painful swelling for 2 months due to kerion Celsi which may be associated with treatment like topical minoxidil, antibiotic and corticosteroid previously. The patient was treated with oral Itraconazole initially without success but cured by Terbinafine eventually. It’s very interesting that the patient caught kerion celsi secondary to a four-month history of hair loss due to black dot tinea capitis.

Functional characterization of African swine fever virus I329L gene by transcriptome analysis - Xianghan Duan; Yuan Wen; Panxue Wu; Jiangling Peng; Yanlong Zhou; Guoqiang Zhu; Dan Li; Yi Ru; Wenping Yang; Haixue Zheng (Veterinary Microbiology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

The early Late Triassic Yumen mafic rocks in the eastern Tethyan Himalaya: A record of the progressive opening of the Yarlung Zangbo Neo-Tethyan Ocean - Wei-Liang Liu; Zhong-Xi Xia; Yun Zhong; Chris Yakymchuk; Zhou-Rong Cai; He Xiao; Xing Liao; Chi Yan; Ru-Xin Ding; Jin-Nan Liu (Lithos, 2023)

Identifying potential toxic organic substances in leachates from tire wear particles and their mechanisms of toxicity to Scenedesmus obliquus - Jie-Ru Jiang; Zhi-Feng Chen; Xiao-Liang Liao; Qian-Yi Liu; Jia-Ming Zhou; Shi-Ping Ou; Zongwei Cai (Journal of Hazardous Materials, 2023)

Environmental pollutant pre- and polyfluoroalkyl substances are associated with electrocardiogram parameters disorder in adults - Yuan-Yuan Fan; Chu Chu; Yun-Ting Zhang; Kun Zhao; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Lu-Yin Wu; Li-Zi Lin; Ru-Qing Liu; Wenru Feng; et al. (Journal of Hazardous Materials, 2023)

Enhancing fiber–matrix interface permeability resistance of natural fiber-reinforced, bio-cemented sand by CaCO 3 seed pretreatment - Liang Guo; Qichen Dai; Xingzhu Lin; Yuhong Jiang; Baoquan Wang; Xiaohua Pan; Yiqi Peng; Guoqiang Zhao; Yi Ru; Liye Zhou (Geomechanics for Energy and the Environment, 2023)

Enhanced catalytic nitrophenol reduction via highly porous hollow silica nanospheres stabilized Au nanoclusters - Ru Hu; Rui Xu; Zizhu Wang; Junyou Wang; Shenghu Zhou (Chemical Engineering Journal, 2023)

Iron reduction in composting environment synergized with quinone redox cycling drives humification and free radical production from humic substances - Ru Sun; Mengxin Fu; Liangcai Ma; Yucheng Zhou; Qunliang Li (Bioresource Technology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

First transcriptome profiling in gill and hepatopancrease tissues of Metapenaeus ensis in response to acute ammonia-N stress - Yun-Dong Li; Meng-Ru Si; Shi-Gui Jiang; Qi-Bin Yang; Song Jiang; Li-Shi Yang; Jian-Hua Huang; Fa-Lin Zhou (Fish & Shellfish Immunology, 2023)

Pollinium development and sporoderm structure of Dendrobium officinale - Yi Feng Cui; Ting Zhou; Ya Ru Wei; De Quan Wang; Wen Yu Liang; Shu Juan Yang (Flora, 2023)

Carbonate-silicate interaction in subducting slabs recorded by Zn isotopes in western Alps metasediments - Yuan-Ru Qu; Sheng-Ao Liu; Vincent Busigny; Ze-Zhou Wang; Fang-Zhen Teng (Earth and Planetary Science Letters, 2023)

Nonagricultural emissions enhance dimethylamine and modulate urban atmospheric nucleation - Yunhua Chang; Qingyang Ling; Xinlei Ge; Xiangyang Yuan; Shengqian Zhou; Kai Cheng; Jianjiong Mao; Dandan Huang; Qingyao Hu; Jun Lu; Shijie Cui; Yaqing Gao; et al. (Science Bulletin, 2023)

Planning the temporary takeoff/landing site’s location for a pesticide spraying helicopter based on an intelligent fusion algorithm - Shuping Fang; Yu Ru; Chenming Hu; Fengbo Yang; Jiangkun Xue; Jie Zhou (Computers and Electronics in Agriculture, 2023)

Chronology analysis of huge landslide based on ESR dating materials on sliding face in carbonate areas of south eastern Tibet - Chun-Ru Liu; Ying-Ying Tian; Hao Ji; Xi Ma; Chuan-Yi Wei; Jia-Xiang Dang; Gong-Ming Yin; Yong-Sheng Zhou; Ren-Mao Yuan (Quaternary Geochronology, 2023)

Polysaccharides from the hard shells of Juglans regia L. modulate intestinal function and gut microbiota in vivo - Xiaoyu Li; Siying An; Zhen Luo; Peng Zhou; Lu Wang; Ru Feng (Food Chemistry, 2023)

A micromechanical investigation of sand–rubber mixtures using the discrete element method - Ru Fu; Bo Yang; Xinli Hu; Bo Zhou; Matthew Richard Coop (Engineering Geology, 2023)

Prenatal diagnosis in the fetal hyperechogenic kidneys: assessment using chromosomal microarray analysis and exome sequencing - Ruibin Huang; Fang Fu; Hang Zhou; Lu Zhang; Tingying Lei; Ken Cheng; Shujuan Yan; Fei Guo; You Wang; Chunling Ma; Ru Li; Qiuxia Yu; et al. (Human Genetics, 2023)

Study on Mechanical Property of Coal-Rock Combination Under Different Unloading Confining Pressure Rate - Shanchao Hu; Xuedong Zhou; Wenkai Ru; Jinming Han; Shihao Guo; Chenxi Zhang; Lei Yang (Geotechnical and Geological Engineering, 2023)

Atmospheric solids analysis probe-mass spectrometry (ASAP-MS) as a rapid fingerprinting technique to differentiate the harvest seasons of Tieguanyin oolong teas - Hui Ru Tan; Li Yan Chan; Adabelle Ong; Yong-Quan Xu; Xue-Bo Zhang; Weibiao Zhou (Food Chemistry, 2023)

Remediating flooding paddy soils with schwertmannite greatly reduced arsenic accumulation in rice (Oryza sativa L.) but did not decrease the utilization efficiency of P fertilizer - Ru Wang; Yinglin Guo; Yang Song; Yuting Guo; Xiaomeng Wang; Quan Yuan; Zengping Ning; Chengshuai Liu; Lixiang Zhou; Guanyu Zheng (Environmental Pollution, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Glycation of whey protein isolate and stachyose modulates their in vitro digestibility: Promising prebiotics as functional ingredients - Guang-yao Zhang; Cong Sun; Jing-ru Song; Wei-yi Jin; Yue Tang; Da-yong Zhou; Liang Song (Food Bioscience, 2023)

Genomic vulnerability to climate change in Quercus acutissima , a dominant tree species in East Asian deciduous forests - Shuai Yuan; Yong Shi; Biao‐Feng Zhou; Yi‐Ye Liang; Xue‐Yan Chen; Qing‐Qing An; Yan‐Ru Fan; Zhao Shen; Pär K. Ingvarsson; Baosheng Wang (Molecular Ecology, 2023)
Understanding the evolutionary processes that shape the landscape of genetic variation and influence the response of species to future climate change is critical for biodiversity conservation. Here, we sampled 27 populations across the distribution range of a dominant forest tree, Quercus acutissima , in East Asia, and applied genome‐wide analyses to track the evolutionary history and predict the fate of populations under future climate. We found two genetic groups (East and West) in Q. acutissima that diverged during Pliocene. We also found a heterogeneous landscape of genomic variation in this species, which may have been shaped by population demography and linked selections. Using genotype‐environment association analyses, we identified climate‐associated SNPs in a diverse set of genes and functional categories, indicating a model of polygenic adaptation in Q. acutissima . We further estimated three genetic offset metrics to quantify genomic vulnerability of this species to climate change due to the complex interplay between local adaptation and migration. We found that marginal populations are under higher risk of local extinction because of future climate change, and may not be able to track suitable habitats to maintain the gene–environment relationships observed under the current climate. We also detected higher reverse genetic offsets in northern China, indicating that genetic variation currently present in the whole range of Q. acutissima may not adapt to future climate conditions in this area. Overall, this study illustrates how evolutionary processes have shaped the landscape of genomic variation, and provides a comprehensive genome‐wide view of climate maladaptation in Q. acutissima .

Efficient coupling of sulfadiazine removal with microalgae lipid production in a membrane photobioreactor - Feng Gao; Jin-Long Zhou; Yu-Ru Zhang; Ashiwin Vadiveloo; Qing-Guo Chen; Jun-Zhi Liu; Qiao Yang; Ya-Ming Ge (Chemosphere, 2023)

Characterization of microbial community, ecological functions and antibiotic resistance in estuarine plastisphere - Le-Yang Yang; Xin-Rong Huang; Roy Neilson; Shu-Yi-Dan Zhou; Zhao-Lei Li; Xiao-Ru Yang; Xiao-Xuan Su (Science of The Total Environment, 2023)

Whole exome sequencing improves genetic diagnosis of fetal clubfoot - Ruibin Huang; Hang Zhou; Chunling Ma; Fang Fu; Ken Cheng; You Wang; Ru Li; Tingying Lei; Qiuxia Yu; Dan Wang; Shujuan Yan; Xin Yang; et al. (Human Genetics, 2023)

Effect of phenol formaldehyde-associated microplastics on soil microbial community, assembly, and functioning - Hu Li; Qiu-Ping Luo; Sha Zhao; Yan-Yan Zhou; Fu-Yi Huang; Xiao-Ru Yang; Jian-Qiang Su (Journal of Hazardous Materials, 2023)

Heterogeneous Fenton for Removal Rhodamine-B by Iron-bearing Attapulgite Granular Catalysts - Peiguo Zhou; Wenjing Yang; Tianyu Lu; Xin Ru; Zongbiao Dai; Meshack Appiah Ofori; Jiaxin Hou (Water, Air, & Soil Pollution, 2023)

Portal vein tumor thrombosis in hepatocellular carcinoma: molecular mechanism and therapy - Xing-Hao Zhou; Jing-Ru Li; Tang-Hui Zheng; Hong Chen; Chen Cai; Sheng-Long Ye; Bo Gao; Tong-Chun Xue (Clinical & Experimental Metastasis, 2023)

Contribution of Tibetan Plateau ecosystems to local and remote precipitation through moisture recycling - Yan Li; Ru Xu; Kun Yang; Yanxu Liu; Shuai Wang; Sha Zhou; Zhao Yang; Xiaoming Feng; Chunyang He; Zhengjie Xu; Wenwu Zhao (Global Change Biology, 2023)
The ecosystems of the Tibetan Plateau (TP) provide multiple important ecosystem services that benefit both local populations and those beyond, such as through climate regulation services on precipitation for East Asia and China. However, the precipitation regulation service of the TP ecosystems for supplying moisture and maintaining precipitation is yet to be evaluated. In this study, we used the moisture recycling framework and a moisture tracking model to quantify the precipitation regulation services of TP ecosystems for their contribution to precipitation. We found TP ecosystems contributed substantially to local and downwind precipitation, with a contribution of 221 mm/year for the TP and neighboring areas through evapotranspiration (ET) (104 mm/year through transpiration), declined to

Quinone redox cycling drives lignocellulose depolymerization and degradation in composting environments based on metagenomics analysis - Ru Sun; Ziyi Cao; Xiaoli Wen; Liangcai Ma; Yucheng Zhou; Jixuan Li; Mengxin Fu; Pengfei Zhu; Kecheng Li; Qunliang Li (Science of The Total Environment, 2023)

Comparison of biochemical composition, nutritional quality, and metals concentrations between males and females of three different Crassostrea sp. - Yanping Qin; Ru Li; Qingliang Liao; Gongpengyang Shi; Yinyin Zhou; Weitao Wan; Jun Li; Haitao Ma; Yuehuan Zhang; Ziniu Yu (Food Chemistry, 2023)

Association between long-term ambient ozone exposure and attention-deficit/hyperactivity disorder symptoms among Chinese children - Peien Zhou; Wangjian Zhang; Yu-Jie Xu; Ru-Qing Liu; Zhengmin Qian; Stephen Edward McMillin; Elizabeth Bingheim; Li-Zi Lin; Xiao-Wen Zeng; Bo-Yi Yang; Li-Wen Hu; Wen Chen; et al. (Environmental Research, 2023)

Temporal tuning of illuminance and spectrum: Effect of a full-day dynamic lighting pattern on well-being, performance and sleep in simulated office environment - Taotao Ru; Maaike E. Kompier; Qingwei Chen; Guofu Zhou; Karin C.H.J. Smolders (Building and Environment, 2023)

Efficient microalgal lipid production driven by salt stress and phytohormones synergistically - Zi-Yan Yang; Kai-Xuan Huang; Yu-Ru Zhang; Lei Yang; Jin-Long Zhou; Qiao Yang; Feng Gao (Bioresource Technology, 2023)

Cryo-EM structures reveal the dynamic transformation of human alpha-2-macroglobulin working as a protease inhibitor - Xiaoxing Huang; Youwang Wang; Cong Yu; Hui Zhang; Qiang Ru; Xinxin Li; Kai Song; Min Zhou; Ping Zhu (Science China Life Sciences, 2022)

Sulfur defect and Fe(III) (hydr)oxides on pyrite surface mediate tylosin adsorption in lake water: effect of solution chemistry and dissolved organic matter - Qian Zhang; Jinwen Zhou; Lishan Zhang; Shan Zhong; Xuan Ru; Xiaohua Shu (Environmental Science and Pollution Research, 2022)

Rapid Effect of Enriched Nitrogen on Soybean Nitrogen Uptake, Distribution, and Assimilation During Early Flowering Stage - Hongli Zhou; Qiang Zhao; Ru He; Wei Zhang; Huijun Zhang; Haiying Wang; Xue Ao; Xingdong Yao; Futi Xie (Journal of Soil Science and Plant Nutrition, 2022)

Effects of passenger blockage on smoke flow properties in subway station fires - Fan Wu; Yan Wang; Ru Zhou; Juncheng Jiang (Environmental Science and Pollution Research, 2022)

Deciphering the Heterogeneity of Mitochondrial Functions During Hematopoietic Lineage Differentiation - Haoyue Liang; Shuxu Dong; Weichao Fu; Sen Zhang; Wenying Yu; Fang Dong; Baolin He; Jinhong Wang; Yingdai Gao; Yuan Zhou; Yongxin Ru (Stem Cell Reviews and Reports, 2022)

The correlation of fibrinogen-like protein-1 expression with the progression and prognosis of hepatocellular carcinoma - Nanni Hua; Anxian Chen; Chen Yang; Hui Dong; Xianglei He; Guoqing Ru; Xiangmin Tong; Feifei Zhou; Shibing Wang (Molecular Biology Reports, 2022)
Background Fibrinogen-like-protein 1 (FGL1), a member of the fibrinogen-related protein (FREP) family, is a major ligand of the immune inhibitory receptor lymphocyte-activation gene 3 (LAG-3). While FGL1 is strongly implicated in the development and prognosis of a variety of diseases, its role in hepatocellular carcinoma (HCC) is still disputed. Therefore, the role of FGL1 expression in the progression and prognosis of HCC was investigated. Methods and results In the present study, bioinformatics analysis was first used to probe the expression profile of FGL1 in multiple malignant tumor tissues and paired normal tissues, and to explore the possible relationship between FGL1 and prognosis of HCC patients. Thereafter, the expression levels of FGL1 were determined and compared in human HCC cell lines, HCC tissues, peri-tumor tissues and normal liver tissues by western blot analysis. Furthermore, tissue microarrays were used to detect the expression of FGL1 through immunohistochemical staining and to verify whether the FGL1 expression level was associated with clinicopathological features and the prognosis of HCC patients. The results showed that FGL1 was downregulated significantly in most of the HCC cells lines and HCC tissues, corresponding to the results of the bioinformatics and western blot analyses. FGL1 expression level in HCC was found to be correlated to Edmondson grade and metastasis of the HCC. Additionally, high FGL1 expression was associated with better overall survival in HCC patients, suggesting that FGL1 could function as a tumor suppressor. Conclusions The expression level of FGL1 can be correlated with the progression and prognosis of HCC, suggesting its potential as a prognostic biomarker.

Detection of bloom-forming dinoflagellates Karenia mikimotoi and Prorocentrum donghaiense using qPCR assays - Xiao-Kun Hu; Zhuo-Ru Lin; Qing-Chun Zhang; Fan-Zhou Kong; Jing-Yi Cen; Yu-Lan Zeng; Ren-Cheng Yu (Journal of Applied Phycology, 2022)

Correction to: Inhibitory effects of aloperine on voltage-gated Na+ channels in rat ventricular myocytes - Meng-ting Li; Ya-ya Du; Fei Zhong; Jie-ru Wang; You-wei Gu; Yue Zhang; Xuan-tong Huang; Yi-zhou Deng; Zheng-xin Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Genome-Wide Identification and Expression Profiling of the bHLH Transcription Factor Gene Family in Saccharum spontaneum Under Bacterial Pathogen Stimuli - Ahmad Ali; Talha Javed; Uroosa Zaheer; Jing-Ru Zhou; Mei-Ting Huang; Hua-Ying Fu; San-Ji Gao (Tropical Plant Biology, 2021)

Inhibitory effects of aloperine on voltage-gated Na+ channels in rat ventricular myocytes - Meng-ting Li; Ya-ya Du; Fei Zhong; Jie-ru Wang; You-wei Gu; Yue Zhang; Xuan-tong Huang; Yi-zhou Deng; Zheng-xin Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

OsGSTU6 Contributes to Cadmium Stress Tolerance in Rice by Involving in Intracellular ROS Homeostasis - Xiu-Qing Jing; Meng-Ru Zhou; Xiu-Min Nie; Lu Zhang; Peng-Tao Shi; Abdullah Shalmani; Hai Miao; Wen-Qiang Li; Wen-Ting Liu; Kun-Ming Chen (Journal of Plant Growth Regulation, 2021)

Molecular epidemiological characteristics of echovirus 6 in mainland China: extensive circulation of genotype F from 2007 to 2018 - Wenjun Cheng; Tianjiao Ji; Shuaifeng Zhou; Yong Shi; Lili Jiang; Yong Zhang; Dongmei Yan; Qian Yang; Yang Song; Ru Cai; Wenbo Xu (Archives of Virology, 2021)
Echovirus 6 (E6) is associated with various clinical diseases and is frequently detected in environmental sewage. Despite its high prevalence in humans and the environment, little is known about its molecular phylogeography in mainland China. In this study, 114 of 21,539 (0.53%) clinical specimens from hand, foot, and mouth disease (HFMD) cases collected between 2007 and 2018 were positive for E6. The complete VP1 sequences of 87 representative E6 strains, including 24 strains from this study, were used to investigate the evolutionary genetic characteristics and geographical spread of E6 strains. Phylogenetic analysis based on VP1 nucleotide sequence divergence showed that, globally, E6 strains can be grouped into six genotypes, designated A to F. Chinese E6 strains collected between 1988 and 2018 were found to belong to genotypes C, E, and F, with genotype F being predominant from 2007 to 2018. There was no significant difference in the geographical distribution of each genotype. The evolutionary rate of E6 was estimated to be 3.631 × 10 -3 substitutions site -1 year -1 (95% highest posterior density [HPD]: 3.2406 × 10 -3 -4.031 × 10 -3 substitutions site -1 year -1 ) by Bayesian MCMC analysis. The most recent common ancestor of the E6 genotypes was traced back to 1863, whereas their common ancestor in China was traced back to around 1962. A small genetic shift was detected in the Chinese E6 population size in 2009 according to Bayesian skyline analysis, which indicated that there might have been an epidemic around that year.

Selective Ferroptosis Inhibitor Liproxstatin-1 Attenuates Neurological Deficits and Neuroinflammation After Subarachnoid Hemorrhage - Yang Cao; Yin Li; Chao He; Feng Yan; Jian-Ru Li; Hang-Zhe Xu; Jian-Feng Zhuang; Hang Zhou; Yu-Cong Peng; Xiong-Jie Fu; Xiao-Yang Lu; Yuan Yao; et al. (Neuroscience Bulletin, 2021)

Haplotype networks of Phycocalidia tanegashimensis (Bangiales, Rhodophyta) indicate a probable invasion from the South China Sea to Brazil - Wan Zhao; Lei Dong; Dang Diem Hong; Juliet Brodie; Wei-Zhou Chen; Dam Duc Tien; Wei Zhou; Qin-Qin Lu; Mei-Ru Zhang; Li-En Yang (Marine Biodiversity, 2021)

Effects of Grazing, Wind Erosion, and Dust Deposition on Plant Community Composition and Structure in a Temperate Steppe - Mengmei Zheng; Jian Song; Jingyi Ru; Zhenxing Zhou; Mingxing Zhong; Lin Jiang; Dafeng Hui; Shiqiang Wan (Ecosystems, 2021)

Nonadditive and Legacy Effects of Spring and Autumn Warming on Soil Respiration in an Old-Field Grassland - Shijie Ning; Jian Song; Jingyi Ru; Zhenxing Zhou; Jiajia Zhang; Xianghui Liu; Yan Hui; Yafei Ma; Shiqiang Wan (Ecosystems, 2021)

Correction to: Involvement of proBDNF in Monocytes/Macrophages with Gastrointestinal Disorders in Depressive Mice - Yun-Qing Yu; Yan-Ling Zhang; Zhe Wang; Yu Liu; Hui Li; Chang-Qi Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2020)

Involvement of proBDNF in Monocytes/Macrophages with Gastrointestinal Disorders in Depressive Mice - Yun-Qing Yu; Yan-Ling Zhang; Zhe Wang; Yu Liu; Hui Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2020)

Elevated ROS depress mitochondrial oxygen utilization efficiency in cardiomyocytes during acute hypoxia - Ru-Zhou Zhao; Xiao-Bo Wang; Shuai Jiang; Ning-Yu Ru; Bo Jiao; Yun-Ying Wang; Zhi-Bin Yu (Pflügers Archiv - European Journal of Physiology, 2020)

Low Serum Uric Acid Levels Promote Hypertensive Intracerebral Hemorrhage by Disrupting the Smooth Muscle Cell-Elastin Contractile Unit and Upregulating the Erk1/2-MMP Axis - Ning Xiao; Tian-long Liu; Hao Li; Hao-chen Xu; Jing Ge; Hong-yan Wen; Cong-xia Bai; Li Song; Ying-ying Sun; Yin-hui Zhang; Ru-tai Hui; Wei-hua Song; et al. (Translational Stroke Research, 2020)

Emerging relationship between RNA helicases and autophagy - Miao-miao Zhao; Ru-sha Wang; Yan-lin Zhou; Zheng-gang Yang (Journal of Zhejiang University-SCIENCE B, 2020)

Mining-induced mechanical response of coal and rock at different depths: a case study in the Pingdingshan Mining Area - Ersheng Zha; Shiyong Wu; Zetian Zhang; Ru Zhang; Man Wang; Jifang Zhou; Zhaopeng Zhang; Zheqiang Jia (Arabian Journal of Geosciences, 2020)

Impaired Parahippocampal Gyrus–Orbitofrontal Cortex Circuit Associated with Visuospatial Memory Deficit as a Potential Biomarker and Interventional Approach for Alzheimer Disease - Lin Zhu; Zan Wang; Zhanhong Du; Xinyang Qi; Hao Shu; Duan Liu; Fan Su; Qing Ye; Xuemei Liu; Zheng Zhou; Yongqiang Tang; Ru Song; et al. (Neuroscience Bulletin, 2020)

Expression, purification, and characterization of a new Glucosyltransferase involved in the third step of O-antigen repeating-unit biosynthesis of Escherichia coli O152 - Chenying Dong; Diange Li; Ru Wang; Jian Chu; Zhongying Gong; Dawei Zhou (Glycoconjugate Journal, 2020)

Genome-Wide Identification of Malectin/Malectin-Like Domain Containing Protein Family Genes in Rice and Their Expression Regulation Under Various Hormones, Abiotic Stresses, and Heavy Metal Treatments - Xiu-Qing Jing; Abdullah Shalmani; Meng-Ru Zhou; Peng-Tao Shi; Izhar Muhammad; Yi Shi; Rahat Sharif; Wen-Qiang Li; Wen-Ting Liu; Kun-Ming Chen (Journal of Plant Growth Regulation, 2020)

Betulinic acid attenuates lipopolysaccharide-induced vascular hyporeactivity in the rat aorta by modulating Nrf2 antioxidative function - Yao-Yao Bai; Dong Yan; Hui-Ying Zhou; Wei-Xin Li; Yang-Yun Lou; Xin-Ru Zhou; Ling-Bo Qian; Chi Xiao (Inflammopharmacology, 2020)

Applying multivariate statistics for identification of groundwater chemistry and qualities in the Sugan Lake Basin, Northern Qinghai-Tibet Plateau, China - Juan Xiang; Jun-ju Zhou; Jun-cang Yang; Mei-hua Huang; Wei Feng; Qiao-qiao Li; Dong-xiang Xue; Ya-ru Zhao; Guo-feng Zhu (Journal of Mountain Science, 2020)

Asymmetric responses of plant community structure and composition to precipitation variabilities in a semi-arid steppe - Mingxing Zhong; Jian Song; Zhenxing Zhou; Jingyi Ru; Mengmei Zheng; Ying Li; Dafeng Hui; Shiqiang Wan (Oecologia, 2019)

Upregulation of proBDNF in the Mesenteric Lymph Nodes in Septic Mice - Zhe Wang; Jia-Li Wu; Feng Zhong; Yu Liu; Yun-Qing Yu; Jing-Jing Sun; Shuang Wang; Hui Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2019)

Mixed phase nano–CdS supported on activated biomass carbon as efficient visible light–driven photocatalysts - Feng-Ying Cai; Yu-Qing Zhang; Jun-Tao Wang; Jun-Ru Zhou; Hai-Lei Cao; Jian Lü (Environmental Science and Pollution Research, 2019)

Cytoplasmic SIRT1 inhibits cell migration and invasion by impeding epithelial–mesenchymal transition in ovarian carcinoma - Tong Yang; Ru Zhou; Shentong Yu; Shuhong Yu; Zhuqing Cui; Peizhen Hu; Jinsong Liu; Qing Qiao; Jing Zhang (Molecular and Cellular Biochemistry, 2019)

The Neuroprotective Effect of L-Stepholidine on Methamphetamine-Induced Memory Deficits in Mice - Mei Zhou; Xiaokang Gong; Qin Ru; Qi Xiong; Lin Chen; Yuanren Si; Huaqiao Xiao; Chaoying Li (Neurotoxicity Research, 2019)

Selenium (Se) Does Not Reduce Cadmium (Cd) Uptake and Translocation in Rice (Oryza sativa L.) in Naturally Occurred Se-Rich Paddy Fields with a High Geological Background of Cd - Bei-Bei Yang; Cheng Yang; Zong-Yuan Shao; Hao Wang; Shu-Ting Zan; Meng Zhu; Shou-Biao Zhou; Ru-Yi Yang (Bulletin of Environmental Contamination and Toxicology, 2019)

CBR-based integration of a hydrodynamic and water quality model and GIS—a case study of Chaohu City - Zhenliang Liao; Can Zhou; Wenchong Tian; Tiantian Hu; Ru Guo (Environmental Science and Pollution Research, 2019)

Dispersion and attenuation of compressional waves in tight oil reservoirs: Experiments and simulations - Ru-Peng Ma; Jing Ba; José Maria Carcione; Xin Zhou; Fan Li (Applied Geophysics, 2019)

Preventive agents for neurodegenerative diseases from resin of Dracaena cochinchinensis attenuate LPS-induced microglia over-activation - Yingzhan Tang; Guangyue Su; Ning Li; Wenjie Li; Gang Chen; Ru Chen; Di Zhou; Yue Hou (Journal of Natural Medicines, 2019)

Transplantation of UC-MSCs on collagen scaffold activates follicles in dormant ovaries of POF patients with long history of infertility - Lijun Ding; Guijun Yan; Bin Wang; Lu Xu; Yan Gu; Tong Ru; Xiaoying Cui; Lei Lei; Jingyu Liu; Xiaoqiang Sheng; Bin Wang; Chunxue Zhang; et al. (Science China Life Sciences, 2018)

High-degree and broad-spectrum resistance mediated by a combination of NIb siRNA and miRNA suppresses replication of necrotic and common strains of potato virus Y - Ru Yu; Caixia Chen; Weilin Cao; Hongmei Liu; Shumei Zhou; Yunzhi Song; Changxiang Zhu (Archives of Virology, 2018)

Luteolin alleviates cardiac ischemia/reperfusion injury in the hypercholesterolemic rat via activating Akt/Nrf2 signaling - Jin-Ting Yang; Jue Wang; Xin-Ru Zhou; Chi Xiao; Yang-Yun Lou; Li-Hui Tang; Feng-Jiang Zhang; Ling-Bo Qian (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Soil physicochemical properties and vegetation structure along an elevation gradient and implications for the response of alpine plant development to climate change on the northern slopes of the Qilian Mountains - Yong-sheng Yang; Li Zhang; Hong-qin Li; Hui-dan He; Ya-xi Wei; Jin Luo; Guang-ru Zhang; Yu-ru Huang; Ying-nian Li; Hua-kun Zhou (Journal of Mountain Science, 2018)

Genetic analysis of three porcine bocaparvoviruses and identification of a natural recombinant breakpoint in NS1 - Yu Zhou; Jia Xu; Shi-Kang Zhu; Qing-Feng Meng; Zhi-Xiong Lin; Ru Chen; Ai-Dong Qian (Archives of Virology, 2018)

Shifts of growing‐season precipitation peaks decrease soil respiration in a semiarid grassland - Jingyi Ru; Yaqiong Zhou; Dafeng Hui; Mengmei Zheng; Shiqiang Wan (Global Change Biology, 2018)
Changing precipitation regimes could have profound influences on carbon (C) cycle in the biosphere. However, how soil C release from terrestrial ecosystems responds to changing seasonal distribution of precipitation remains unclear. A field experiment was conducted for 4 years (2013–2016) to examine the effects of altered precipitation distributions in the growing season on soil respiration in a temperate steppe in the Mongolian Plateau. Over the 4 years, both advanced and delayed precipitation peaks suppressed soil respiration, and the reductions mainly occurred in August. The decreased soil respiration could be primarily attributable to water stress and subsequently limited plant growth (community cover and belowground net primary productivity) and soil microbial activities in the middle growing season, suggesting that precipitation amount in the middle growing season is more important than that in the early, late, or whole growing seasons in regulating soil C release in grasslands. The observations of the additive effects of advanced and delayed precipitation peaks indicate semiarid grasslands will release less C through soil respiratory processes under the projected seasonal redistribution of precipitation in the future. Our findings highlight the potential role of intra‐annual redistribution of precipitation in regulating ecosystem C cycling in arid and semiarid regions.

TNF-α/TNFR1 Signaling is Required for the Full Expression of Acute and Chronic Itch in Mice via Peripheral and Central Mechanisms - Xiuhua Miao; Ya Huang; Teng-Teng Liu; Ran Guo; Bing Wang; Xue-Long Wang; Li-Hua Chen; Yan Zhou; Ru-Rong Ji; Tong Liu (Neuroscience Bulletin, 2018)

Echinacoside, a phenylethanoid glycoside from Cistanche deserticola, extends lifespan of Caenorhabditis elegans and protects from Aβ-induced toxicity - Wei Chen; Hong-Ru Lin; Cong-Min Wei; Xiao-Hua Luo; Meng-Lu Sun; Zhen-Zhou Yang; Xin-Yan Chen; Hong-Bing Wang (Biogerontology, 2018)

Influence of Rapeseed Cake on Iron Plaque Formation and Cd Uptake by Rice (Oryza sativa L.) Seedlings Exposed to Excess Cd - Wen-Tao Yang; Hang Zhou; Jiao-Feng Gu; Qing-ru Zeng; Bo-Han Liao (Bulletin of Environmental Contamination and Toxicology, 2017)

Spatial distribution modeling of temperature increase for the uplifted mountain terrains and its characteristics in Southwest China - Yan-xia Wang; Kun Ding; Mao-biao Li; Ru-liang Zhou (Journal of Mountain Science, 2017)

Melatonin increases reactive aggression in humans - Jinting Liu; Ru Zhong; Wei Xiong; Haibo Liu; Christoph Eisenegger; Xiaolin Zhou (Psychopharmacology, 2017)

Substitution mapping of QTLs controlling seed dormancy using single segment substitution lines derived from multiple cultivated rice donors in seven cropping seasons - Yuliang Zhou; Yuehua Xie; Jinling Cai; Chunbao Liu; Haitao Zhu; Ru Jiang; Yueying Zhong; Guoliang Zhang; Bin Tan; Guifu Liu; Xuelin Fu; Ziqiang Liu; et al. (Theoretical and Applied Genetics, 2017)

The pharmacological activities and mechanisms of artemisinin and its derivatives: a systematic review - Yi-Fei Dai; Wei-Wei Zhou; Jing Meng; Xin-Liang Du; Yun-Peng Sui; Li Dai; Peng-Qian Wang; Hai-Ru Huo; Feng Sui (Medicinal Chemistry Research, 2017)

Cd Content in Sugarcane and Its Relationship with Soil Factors - Hui-Ping Ou; Liu-Qiang Zhou; Xi-Hui Liu; Jin-Sheng Huang; Yan Zeng; Ru-Lin Xie; Xiao-Hui Zhu; Hong-Wei Tan; Yang-Rui Li (Sugar Tech, 2017)

Transplantation of collagen scaffold with autologous bone marrow mononuclear cells promotes functional endometrium reconstruction via downregulating ΔNp63 expression in Asherman’s syndrome - Guangfeng Zhao; Yun Cao; Xianghong Zhu; Xiaoqiu Tang; Lijun Ding; Haixiang Sun; Juan Li; Xinan Li; Chenyan Dai; Tong Ru; Hui Zhu; Jingjie Lu; et al. (Science China Life Sciences, 2017)

RhoB/ROCK mediates oxygen–glucose deprivation-stimulated syncytiotrophoblast microparticle shedding in preeclampsia - Jian Han; Bo-ping Yang; Yi-lin Li; Hong-mei Li; Xiu-hui Zheng; Li-li Yu; Qiong Zhang; Ying-ru Zheng; Ping Yi; Li Li; Jian-xin Guo; Yuan-guo Zhou (Cell and Tissue Research, 2016)

Peripheral Blood MicroRNA Expression Profiles in Alzheimer’s Disease: Screening, Validation, Association with Clinical Phenotype and Implications for Molecular Mechanism - Ru-Jing Ren; Yong-Fang Zhang; Eric B. Dammer; Yi Zhou; Li-ling Wang; Xiao-Hong Liu; Bei-Lei Feng; Guo-Xin Jiang; Sheng-Di Chen; Gang Wang; Qi Cheng (Molecular Neurobiology, 2016)

Trans-cinnamaldehyde protected PC12 cells against oxygen and glucose deprivation/reperfusion (OGD/R)-induced injury via anti-apoptosis and anti-oxidative stress - Xue Qi; Ru Zhou; Yue Liu; Jing Wang; Wan-Nian Zhang; Huan-Ran Tan; Yang Niu; Tao Sun; Yu-Xiang Li; Jian-Qiang Yu (Molecular and Cellular Biochemistry, 2016)

A genome-wide analysis of the ASYMMETRIC LEAVES2/LATERAL ORGAN BOUNDARIES (AS2/LOB) gene family in barley (Hordeum vulgare L.) - Bao-jian Guo; Jun Wang; Shen Lin; Zheng Tian; Kai Zhou; Hai-ye Luan; Chao Lyu; Xin-zhong Zhang; Ru-gen Xu (Journal of Zhejiang University-SCIENCE B, 2016)

Impacts of rapeseed dregs on Cd availability in contaminated acid soil and Cd translocation and accumulation in rice plants - Wen-Tao Yang; Jiao-Feng Gu; Jia-Ling Zou; Hang Zhou; Qing-Ru Zeng; Bo-Han Liao (Environmental Science and Pollution Research, 2016)

Fast Marching and Runge–Kutta Based Method for Centreline Extraction of Right Coronary Artery in Human Patients - Hengfei Cui; Desheng Wang; Min Wan; Jun-Mei Zhang; Xiaodan Zhao; Ru San Tan; Weimin Huang; Wei Xiong; Yuping Duan; Jiayin Zhou; Tong Luo; Ghassan S. Kassab; et al. (Cardiovascular Engineering and Technology, 2016)

Pertrogenesis and tectonic implications of the late Jurassic basic rocks from the northern Shi‐Hang zone, Southeast China - Qing Zhou; Yao–hui Jiang; Shi–yong Liao; Peng Zhao; Ru–ya Jia; Zheng Liu; Guo–chang Wang; Chun–yu Ni (Island Arc, 2016)
The tectonic setting of the late mesozoic of South China is in a debate between two schools of thought: an intra‐continental rift zone along a passive continental margin or active rifting associated with subduction of the paleo‐Pacific Plate. In this study, we present new sensitive high‐resolution ion microprobe (SHRIMP) U‐Pb zircon ages, along with geochemical data of three basic dikes that cross‐cut the Dexing porphyry copper deposit. The deposit is the largest of its kind in eastern China and part of large scale mineralization associated with Mesozoic magmatic activity in the area. Our results indicate that the dikes were emplaced in the Late Jurassic with an average U‐Pb age of 153.5 ± 2.4 Ma. The intrusions have bulk ε Nd (t) of ca +0.7 and zircon ε Hf (t) value of +1.54 to +6.92. Based on relatively enriched light rare earth elements (LREE) and depleted high‐field‐strength elements (HFSE) abundances with pronounced negative Ta–Nb, Hf–Zr and Ti anomalies in multi‐element diagrams, we propose that these dikes were derived from a subduction‐modified lithospheric mantle source. The variability in Hf isotopes identifies some degree of crustal contaminations. Our data support a scenario with a back‐arc extensional setting or an intra‐arc rift environment associated with the westward subduction of the paleo‐Pacific Plate at or prior to the late Jurassic as the most likely cause for these subduction signatures.

Effect of desiccation in shade on in vitro oocyte maturation and development of the sea cucumber Apostichopus japonicus (Echinodermata: Holothuroidea) - Shilin Liu; Yi Zhou; Tao Zhang; Lina Sun; Xiaoshang Ru; Junhua Li; Hongsheng Yang (Invertebrate Reproduction & Development, 2016)

Neuroprotection of Sevoflurane Against Ischemia/Reperfusion-Induced Brain Injury Through Inhibiting JNK3/Caspase-3 by Enhancing Akt Signaling Pathway - Xiang-Ru Wen; Yan-Yan Fu; Hong-Zhi Liu; Jian Wu; Xiao-Ping Shao; Xun-Bao Zhang; Man Tang; Yue Shi; Kai Ma; Fang Zhang; Yi-Wen Wang; Hui Tang; et al. (Molecular Neurobiology, 2016)

Erratum to: An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2016)

Differential effects of general anesthetics on anxiety-like behavior in formalin-induced pain: involvement of ERK activation in the anterior cingulate cortex - Cong Luo; Yan-Ling Zhang; Wei Luo; Fiona H Zhou; Chang-Qi Li; Jun-Mei Xu; Ru-Ping Dai (Psychopharmacology, 2015)

Identification of geranylgeranyl diphosphate synthase genes from Tripterygium wilfordii - Meng Zhang; Ping Su; Yong-Jin Zhou; Xiu-Juan Wang; Yu-Jun Zhao; Yu-Jia Liu; Yu-Ru Tong; Tian-Yuan Hu; Lu-Qi Huang; Wei Gao (Plant Cell Reports, 2015)

An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2015)
IRF-1, a kind of transcription factor, is expressed in many cell types, except in early embryonal cells. IRF-1 has played an essential role in various physiological and pathological processes, including tumor immune surveillance, viral infection, development of immunity system and pro-inflammatory injury. However, the expression and function of IRF-1 in spinal cord injury (SCI) are still unknown. In this study, we have performed an acute SCI model in adult rats and investigated the dynamic changes of IRF-1 expression in the spinal cord. Western blot have shown that IRF-1 protein levels gradually increased, reaching a peak at day 3 and then gradually declined to a normal level at day 14 after SCI. Double immunofluorescence staining showed that IRF-1 immunoreactivity was found in neurons, but not in astrocytes and microglia. Additionally, colocalization of IRF-1/active caspase-3 was detected in neurons. In vitro, IRF-1 depletion, by short interfering RNA, obviously decreases neuronal apoptosis. In conclusion, this is the first description of IRF-1 expression in spinal cord injury. Our results suggested that IRF-1 might play crucial roles in CNS pathophysiology after SCI.

Protective effects of aloperine on neonatal rat primary cultured hippocampal neurons injured by oxygen–glucose deprivation and reperfusion - Ning-Tian Ma; Ru Zhou; Ren-Yuan Chang; Yin-Ju Hao; Lin Ma; Shao-Ju Jin; Juan Du; Jie Zheng; Cheng-Jun Zhao; Yang Niu; Tao Sun; Wei Li; et al. (Journal of Natural Medicines, 2015)

Model-based meta-analysis of the effects of non-selective and α1-selective GABAA receptor agonists in healthy volunteers - Yu-Peng Ren; Ru-Jia Xie; Scott Marshall; Liang Li; Tian-Yan Zhou; Wei Lu (European Journal of Clinical Pharmacology, 2015)

Tree bark as a biomonitor for the determination of polychlorinated biphenyls and polybrominated diphenyl ethers from Southern Jiangsu, China: levels, distribution, and possible sources - Li Zhou; Liang Dong; Ye-Ru Huang; Shuang-Xin Shi; Li-Fei Zhang; Xiu-Lan Zhang; Wen-Long Yang (Environmental Monitoring and Assessment, 2015)

Changes of polybrominated diphenyl ethers and polychlorinated biphenyls in surface soils from urban agglomeration of the Yangtze River Delta, in China between 2003 and 2012 - Shuang-Xin Shi; Ye-Ru Huang; Li Zhou; Li-Fei Zhang; Liang Dong; Wen-Long Yang; Xiu-Lan Zhang (Environmental Science and Pollution Research, 2015)

Paracercospora dictamnicola sp. nov. from China - Yang-Hui Ou; Ru-Jun Zhou; Jun-Fan Fu; Yue Yuan; Hai-Jiao Xu (Mycological Progress, 2015)

Antitumor Activity of DMAKO-05, a Novel Shikonin Derivative, and Its Metabolism in Rat Liver Microsome - Xu Zhang; Ru-Bing Wang; Wen Zhou; Sui Xiao; Qing-Qing Meng; Shao-Shun Li (AAPS PharmSciTech, 2015)

The relationship between the plant-encoded RNA-dependent RNA polymerase 1 and alternative oxidase in tomato basal defense against Tobacco mosaic virus - Yang-Wen-Ke Liao; Ya-Ru Liu; Jia-Yang Liang; Wen-Ping Wang; Jie Zhou; Xiao-Jian Xia; Yan-Hong Zhou; Jing-Quan Yu; Kai Shi (Planta, 2015)

Rock Burst Intensity Classification Based on the Radiated Energy with Damage Intensity at Jinping II Hydropower Station, China - Bing-Rui Chen; Xia-Ting Feng; Qing-Peng Li; Ru-Zhou Luo; Shaojun Li (Rock Mechanics and Rock Engineering, 2015)

Efficacy of a high-growth reassortant H1N1 influenza virus vaccine against the classical swine H1N1 subtype influenza virus in mice and pigs - Feng Wen; Hai Yu; Fu-ru Yang; Meng Huang; Sheng Yang; Yan-Jun Zhou; Ze-Jun Li; Guang-Zhi Tong (Archives of Virology, 2014)

Rapid development of tissue bank achieved by International Atomic Energy Agency (IAEA) Tissue Banking Programme in China - Yu-Min Zhang; Jian-Ru Wang; Nai-Li Zhang; Xiao-Ming Liu; Mo Zhou; Shao-Ying Ma; Ting Yang; Bao-Xing Li (Cell and Tissue Banking, 2014)

Origin of Middle Cambrian and Late Silurian potassic granitoids from the western Kunlun orogen, northwest China: a magmatic response to the Proto-Tethys evolution - Zheng Liu; Yao-Hui Jiang; Ru-Ya Jia; Peng Zhao; Qing Zhou; Guo-Chang Wang; Chun-Yu Ni (Mineralogy and Petrology, 2014)

Origin of Early Cretaceous high-K calc-alkaline granitoids, western Tibet: implications for the evolution of the Tethys in NW China - Yao-Hui Jiang; Zheng Liu; Ru-Ya Jia; Shi-Yong Liao; Peng Zhao; Qing Zhou (International Geology Review, 2014)

Culture of amelanotic melanocytes derived from human fetal hair follicles - Ru-zhi Zhang; Wen-yuan Zhu; Hong-zhou Li; Dong-zhang Xue; Cong-jun Jiang; Wan Li (In Vitro Cellular & Developmental Biology - Animal, 2013)

Occurrence of rust of Sophora flavescens caused by Uromyces sophorae-flavescentis in China - Ru-Jun Zhou; Jun-Fan Fu; Ning Hao; Zhen Liu; Ying Sun (Phytoparasitica, 2013)

Petrogenesis and tectonic implications of early Silurian high-K calc-alkaline granites and their potassic microgranular enclaves, western Kunlun orogen, NW Tibetan Plateau - Ru-Ya Jia; Yao-Hui Jiang; Zheng Liu; Peng Zhao; Qing Zhou (International Geology Review, 2013)

Construction of multiple shRNAs expression vector that inhibits FUT1 gene expression and production of the transgenic SCNT embryos in vitro - Jian-wen Chen; Yu Zhang; Yuan-liang Zhang; Chao Wei; Xing Liu; Na-ru Zhou; Qing Jia; Yun-sheng Li; Xiao-rong Zhang; Yun-hai Zhang (Molecular Biology Reports, 2013)

Mantle origin of the Dexing porphyry copper deposit, SE China - Qing Zhou; Yao-Hui Jiang; Hui-Hua Zhang; Shi-Yong Liao; Guo-Dong Jin; Peng Zhao; Ru-Ya Jia; Zheng Liu (International Geology Review, 2013)

The mitochondrial genome of the quiet-calling katydids, Xizicus fascipes (Orthoptera: Tettigoniidae: Meconematinae) - MING RU YANG; ZHI JUN ZHOU; YAN LIN CHANG; LE HONG ZHAO (Journal of Genetics, 2012)

Clozapine Protects Dopaminergic Neurons from Inflammation-Induced Damage by Inhibiting Microglial Overactivation - Xiaoming Hu; Hui Zhou; Dan Zhang; Sufen Yang; Li Qian; Hung-Ming Wu; Po-See Chen; Belinda Wilson; Hui-Ming Gao; Ru-band Lu; Jau-Shyong Hong (Journal of Neuroimmune Pharmacology, 2012)

The Activation of NMDA Receptor–ERK Pathway in the Central Amygdala is Required for the Expression of Morphine-Conditioned Place Preference in the Rat - Fang Li; Xiao-Sheng Wang; Ru-Ping Dai; Jian-Yi Zhang; Xin-Fu Zhou; Wei Hao; Chang-Qi Li (Neurotoxicity Research, 2011)

Molecular characterization and expression analysis of elongation factors 1A and 2 from the Pacific white shrimp, Litopenaeus vannamei - Lei Wang; Yuan Liu; Wei-Na Wang; Wei-Jun Mai; Yu Xin; Jun Zhou; Wen-Yin He; An-Li Wang; Ru-Yong Sun (Molecular Biology Reports, 2011)

Characterization of human embryonic stem cell-derived hematopoietic progenitor phenotype - Hai-Yang Zhou; Xiao-Yi Yang; Li-Jian Tao; Yue-Tian Chang; Ru-Ping Dai (In Vitro Cellular & Developmental Biology - Animal, 2010)

Field evaluation of an innovative stormwater treatment device—the StormvaultTM system - Ru Zhang; Wen Bin Zhou; Jing Li; Shaw L. Yu (Environmental Monitoring and Assessment, 2010)

Cloning and characterization of novel low molecular weight glutenin subunit genes from two Aegilops species with the C and D genomes - Peng Chen; Ru Li; Ruiyang Zhou; Zhiguo E; Guangyuan He (Genetic Resources and Crop Evolution, 2010)

Detection of circulating tumor cells in peripheral blood from patients with gastric cancer using microRNA as a marker - Hui Zhou; Jun-Ming Guo; Yan-Ru Lou; Xin-Jun Zhang; Fa-De Zhong; Zhen Jiang; Jia Cheng; Bing-Xiu Xiao (Journal of Molecular Medicine, 2010)

Investigations on boron levels in drinking water sources in China - Ren-ji Xu; Xiao-ru Xing; Qun-fang Zhou; Gui-bin Jiang; Fu-sheng Wei (Environmental Monitoring and Assessment, 2010)

Overexpression of soybean ubiquitin-conjugating enzyme gene GmUBC2 confers enhanced drought and salt tolerance through modulating abiotic stress-responsive gene expression in Arabidopsis - Guo-An Zhou; Ru-Zhen Chang; Li-Juan Qiu (Plant Molecular Biology, 2010)

PI-3 kinase pathway can mediate the effect of TGF-β1 in inducing the expression of SHARP-2 in LLC-PK1 cells - Zhang-fei Shou; Qin Zhou; Jie-ru Cai; Jiang-hua Chen; Kazuya Yamada; Kaoru Miyamoto (Journal of Zhejiang University-SCIENCE B, 2009)

Characterization and SNP Identification of Part of the Goat Melanophilin Gene - Fu-Jun Feng; Xiang-Long Li; Rong-Yan Zhou; Gui-Ru Zheng; Lan-Hui Li; Dong-Feng Li (Biochemical Genetics, 2009)

Phosphorus fractions and adsorption characteristics of floodplain sediments in the lower reaches of the Hanjiang River, China - Jian-ru Tian; Pei-jiang Zhou (Environmental Monitoring and Assessment, 2008)

Effect of Pyrogallol on the Growth and Pigment Content of Cyanobacteria-Blooming Toxic and Nontoxic Microcystis Aeruginosa - Bi-Yun Liu; Pei-Jiang Zhou; Jian-Ru Tian; Shun-Yao Jiang (Bulletin of Environmental Contamination and Toxicology, 2007)

Glutathione S-transferases M1 and T1 polymorphisms and arsenic content in hair and urine in two ethnic clans exposed to indoor combustion of high arsenic coal in Southwest Guizhou, China - Guo-fang Lin; Hui Du; Ji-gang Chen; Hong-chao Lu; Jin-xiang Kai; Yun-shu Zhou; Wei-chao Guo; Xin-jiang Zhang; Da-ru Lu; Klaus Golka; Jian-hua Shen (Archives of Toxicology, 2007)

Nematicidal Resorcylides from the Aquatic Fungus Caryospora callicarpa YMF1.01026 - Jinyan Dong; Yanhui Zhu; Hongchuan Song; Ru Li; Hongping He; Haiyang Liu; Rong Huang; Yongping Zhou; Le Wang; Yi Cao; Keqin Zhang (Journal of Chemical Ecology, 2007)

Roots of pioneer trees in the lower sub-tropical area of Dinghushan, Guangdong, China - Yan-ru Hao; Shao-lin Peng; Jiang-ming Mo; Xin-wei Liu; Zhuo-quan Chen; Kai Zhou; Jin-rong Wu (Journal of Zhejiang University-SCIENCE B, 2006)

Treatment and follow-up of children with transient congenital hypothyroidism - Ru-lai Yang; Zhi-wei Zhu; Xue-lian Zhou; Zheng-yan Zhao (Journal of Zhejiang University-SCIENCE B, 2005)

The effects of vitamin E on non-specific immune response of the juvenile soft-shelled turtle Pelodiscus sinensis - Xian-Qing ZHOU; Cui-Juan NIU; Ru-Yong SUN (Fisheries Science, 2005)

Genetic analysis, molecular tagging and mapping of the thermo-sensitive genic male-sterile gene (wtms1) in wheat - Q. H. Xing; Z. G. Ru; C. J. Zhou; X. Xue; C. Y. Liang; D. E. Yang; D. M. Jin; B. Wang (Theoretical and Applied Genetics, 2003)

Habitat Degradation of Rhinopithecus bieti in Yunnan, China - Wen Xiao; Wei Ding; Liang-Wei Cui; Ru-Liang Zhou; Qi-Kun Zhao (International Journal of Primatology, 2003)

The effect of lanthanide chloride on abscisic acid and electron-transport activity of some crops - Fu Li Zeng; Ming Feng Zhang; Shao Min Zhou; Ji Gui Wu; Ru Wen Deng (Biological Trace Element Research, 1999)